Technoeconomic and life-cycle assessment of multi-product and single-product lignocellulosic biorefineries - Seyedamirreza Babaei; Lauren Philips; Juhee Lee; Eun Joong Oh; Ye Huang; Adriana C. Neves; Yinglei Han; Jikai Zhao (Bioresource Technology, 2026)

Rare earth elements recovery from end-of-life NdFeB magnets towards new applications using design of experiments for leaching process - Ana Paula Silva; Óscar Barros; Pier Parpot; Isabel C. Neves; Teresa Tavares; José Pinheiro-Torres; Bruna Silva (Minerals Engineering, 2026)

Lytic activity of F8-like phage φSPM-1 against One Health lineages of carbapenem-resistant Pseudomonas aeruginosa - Patrícia R. Neves; Karine Dantas; Gregory Melocco; Helena Turano; Fernanda Esposito; Ana C. Gales; Carlo E. Levy; Elsa M. Mamizuka; Nilton Lincopan (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
The increasing resistance of Pseudomonas aeruginosa to carbapenem antibiotics is shifting the landscape of high-risk clones from a strictly hospital-acquired threat to a global pathogen with One Health relevance. Given the limited therapeutic options available, developing new treatments is essential. We previously reported the complete genome sequence of φSPM-1 phage from the family Myoviridae . In this study, we show that φSPM-1 displays lytic activity against hospital and environmental metallo-β-lactamase (MβL)-producing P. aeruginosa and confers a protective effect against lethal infection caused by the high-risk clone ST277 in a Galleria mellonella prophylactic model.

Ionic liquid-based sample pretreatment platforms: comparing solid supports and aqueous biphasic systems for enhanced bioanalytical performance - Maria S.M. Mendes; Hugo Santos; Inês Cruz; Márcia C. Neves; Mara G. Freire; Francisca A. e Silva (Sustainable Chemistry and Pharmacy, 2026)

Incident shortwave radiation at a site in the Lower Amazon: Derivatives from measurements and from MERRA-2 - Antonio M.D. Andrade; Helen N.S. Lima; Arthur W.D. Silva; Diego P. Bezerra; Aurilene B.S. Andrade; Ana V.P. Mendes; Rafael C. Muniz; Theomar T.A.T. Neves; Julio T. Silva (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Spatial Scale Modulates the Effect of Habitat Amount on Diversity Patterns of Arachnid Assemblages Across Different Brazilian Ecosystems - André F. A. Lira; Adriano M. DeSouza; Thayna R. Brito‐Almeida; Hugo L. L. Neves; Gilberto G. Rodrigues; Carlos Henrique De‐Oliveira‐Nogueira; Ubiratã F. Souza; Alessandra R. S. Andrade; Rafael G. Jansen; Ana Lúcia Tourinho; Leonardo S. Carvalho; Laís M. Pordeus; et al. (Journal of Biogeography, 2026)
Aim We evaluated how native vegetation cover influences the diversity of arachnid assemblages across multiple spatial scales in major Brazilian ecosystems. Location Brazil (Amazon and Atlantic rainforests, Cerrado savanna and Caatinga dry forest). Taxon Arachnida (Opiliones, Pseudoscorpiones and Scorpiones). Methods We sampled arachnids at 120 sites using active search and litter sifting. Native vegetation cover was quantified at three spatial scales (100, 200 and 300 m buffers) using GIS data. Assemblage structure was assessed using abundance, species richness, and Hill numbers ( q = 0, 1 and 2). Generalized linear mixed models were used to evaluate responses across taxonomic groups and ecosystems. Results We recorded 3986 individuals from 179 species. Diversity responses to native vegetation cover were taxon‐, ecosystem‐ and scale‐dependent. Positive effects of vegetation cover were stronger and more consistent in rainforest than in savanna and dry forest ecosystems. In rainforests, most responses occurred at smaller spatial scales (100–200 m), whereas no significant effects were detected in the savanna. Opiliones richness showed limited variation with vegetation cover but differed in dominance structure among ecosystems. Scorpion assemblages were characterized by low richness and high dominance, while pseudoscorpions exhibited low evenness in more species‐rich sites, particularly in the Amazon. Main Conclusions Native vegetation cover plays an important role in structuring arachnid diversity in Brazil, but its effects vary across taxa, ecosystems and spatial scales. These findings highlight the need for taxon‐ and scale‐specific conservation strategies and reinforce the importance of multi‐scale approaches to biodiversity conservation in Neotropical landscapes under increasing anthropogenic pressure.

Inclusion of carotenoids and Eicosapentaenoic Acid (EPA) in sea urchin (Paracentrotus lividus) broodstock diets improves gonad development and oocyte quality - A. S. Gomes; A. F. Rodrigues; M. Neves; C. Roseiro; H. Cardoso; A. P. Violante; P. J. Gavaia; C. Suckling; S. Lourenço (Aquaculture International, 2026)

The effect of climate change on the distribution of Amblyomma hebraeum and heartwater in South Africa - Magdaleen P. Wepener; Michiel M. Scholtz; Harold L. Weepener; Luis C. B. G. D. Neves (Tropical Animal Health and Production, 2026)
Historically Amblyomma hebraeum has been found in the north-eastern part of South Africa and along the coastal belt stretching to the Eastern Cape area. A change already noted in the past 20 years has been the increase in distribution area in the Eastern Cape, which now includes a larger inland area. It has been postulated that climate change has brought about a change in the distribution of A. hebraeum and subsequently, its potential tick-borne pathogens (TBP), Ehrlichia ruminantium and Rickettsia africae , in South Africa and that the effects of climate change may lead to further distribution changes in future. Habitat suitability modelling using Maxent software demonstrated that the distribution of A. hebraeum has altered compared to previous predictions done 15 years ago and that by the year 2065, most of the central and eastern parts of South Africa are predicted to have a high habitat suitability index for its presence. This indicates that the potential presence of diseases caused by E. ruminantium and R. africae would have to be considered in these previously unaffected areas when animals or humans show signs of illness. This expanded distribution of A. hebraeum and its TBP could have a substantial health and economic impact in South Africa.

Highly efficient (MFe)zeolite catalysts for nimesulide degradation via Fenton-type oxidation - Carmen S.D. Rodrigues; Susana Costa; Olívia S.G.P. Soares; António M. Fonseca; Pier Parpot; Manuel F.R. Pereira; Luis M. Madeira; Elisabetta Rombi; Isabel C. Neves (Chemical Engineering Journal, 2026)

A Ride in Semi-arid: Evaluation of Remote Sensing-based Indices for the Detection and Monitoring of Surface Water Bodies Under Dry and Wet Periods - Eduardo Gonçalves Patriota; Guillaume Francis Bertrand; Alexandro Medeiros Silva; Natalia Maria Mendes da Silva; Khalil Grisi Velôso Mendes; José Welton Gonçalo de Sousa; Richarde Marques da Silva; Cristiano das Neves Almeida; Cinthia Maria de Abreu Claudino; Carolyne Wanessa Lins de Andrade Farias; Jorge Flávio C. B. C. Silva; Victor Hugo Rabelo Coelho (Water Resources Management, 2026)

Renewable energy consumption, clean technology trade and agricultural productivity in Africa - O. Iwegbu; L. C. B. Cardoso; M. C. R. Neves (International Journal of Energy and Water Resources, 2026)

Scientists’ warning on the global destruction of rock outcrop ecosystems - Luiza F. A. de Paula; Lucas N. Perillo; Gianluigi Ottaviani; Flávio F. Carmo; Mandar N. Datar; Katherine C. Enebeli‐Ekwutoziam; Bruno Fogliani; Stephen D. Hopper; Aboli Kulkarni; Hans Lambers; Rafael F. Magalhães; Frederico S. Neves; et al. (Conservation Biology, 2026)
Rock outcrops are geological formations that harbor a highly specialized biota adapted to harsh environmental conditions that differ from their surrounding landscapes. They are globally distributed, especially in old, highly weathered landscapes, and can function as habitat islands containing high levels of endemism and distinct evolutionary lineages. Despite their ecoevolutionary importance, rock outcrops remain largely overlooked in global conservation policy, ecosystem typologies, and biodiversity monitoring frameworks. Extractive activities directly remove the geological substrate that underpins these habitats, and climate change intensifies drought, heatwaves, and hydrological instability. Rising global demand for energy‐transition metals required for decarbonization is expected to further accelerate these pressures, particularly in biodiverse regions of the Global South where governance is weaker. Given that rock outcrop ecosystems are ecologically and evolutionarily significant, we devised a policy‐relevant conservation roadmap structured around prevention, mitigation, restoration, and governance issues. Priority actions include recognizing rock outcrops as unique ecosystems in global classifications and ecosystem typologies, integrating them into biodiversity monitoring frameworks, and improving the identification of key biodiversity areas and the International Union for Conservation of Nature (IUCN) Red List of Ecosystems assessments. We call for stronger environmental impact assessments, cumulative‐impact evaluations for mining and quarrying projects, and the designation of mining and quarrying exclusion sites of high irreplaceability. Coordinated international policy, improved ecological data, and meaningful engagement with local and Indigenous communities are essential to safeguard these ancient ecosystems before further, irreversible losses occur.

Retraction notice to ‘Aluminum: A potentially toxic metal with dose-dependent effects on cardiac bioaccumulation, mineral distribution, DNA oxidation and microstructural remodeling’ [Environ. Pollut. 242, Part A (2018) 814-826] - Rômulo D. Novaes; Viviane G.S. Mouro; Reggiani V. Gonçalves; Andrea A.S. Mendonça; Eliziária C. Santos; Maria C.Q. Fialho; Mariana Machado-Neves (Environmental Pollution, 2026)

Neotropical ants are at greater risk from global warming in savanna than in adjacent forest - Lino A. Zuanon; Karen C. Neves; Alan N. Andersen; Heraldo L. Vasconcelos (Ecology, 2026)
Determining how the thermal tolerances of species are related to climatic conditions at multiple spatial scales can improve our understanding of species distributions and their vulnerability to climate change. We compare the warming tolerances—a metric of warming vulnerability—of arboreal and ground‐dwelling ants from savanna and adjacent semideciduous forest in Brazil's Cerrado. Warming tolerance was estimated using the difference between an ant's upper thermal limit and a thermal index of its habitat and stratum. We also evaluated if differences in the upper and lower thermal limits of Cerrado ant assemblages conform to the thermal adaptation (TAH) and the niche asymmetry (NAH) hypotheses. We found that the mean critical thermal maximum (CT max ) and range (CT range ) were higher for ants in savanna than in forest, a pattern that is consistent with the TAH as savanna had higher maximum and more variable air temperatures. However, arboreal ants had lower CT min than those on the ground despite the similarities in minimum temperatures between the two strata. CT max was lower for ground than for arboreal ants even though in the savanna (but not in the forest) average maximum air temperatures on the ground were 2°C higher than in trees. Further, the greater heat tolerance of savanna ants was less than the ~7°C difference at the ground stratum in mean maximum temperatures between savanna and forest. A moderate phylogenetic signal was found for CT max , CT min , and CT range . However, accounting for phylogeny did not change our results. Our key finding is that vulnerability to global warming cannot be adequately predicted based on heat tolerance alone—species having a similar CT max can have very different vulnerability to global warming because of differences in exposure to direct insolation of their preferred habitat or stratum. In our study system, savanna ground ants are more vulnerable to global warming compared to ants living on the forest floor or to arboreal ants more generally. This may have important implications for conservation of the Brazilian savanna ant fauna since most Cerrado species, including several endemics, nest and forage on the ground.

Iron-exchanged Y-type zeolites for phosphorus recovery from eutrophic waters: Kinetics and performance in real lake matrix - Anna C.M. Martins; Jéssica T. Santos; Teresa Tavares; António G. Brito; António M. Fonseca; Isabel C. Neves; Gilberto Martins (Journal of Environmental Chemical Engineering, 2026)

Quantifying leaf herbivory: A guide to methodological trade‐offs and best practices - Tatiana Cornelissen; Gisele M. Mendes; Fernando A. O. Silveira; Wesley Dáttilo; Roger Guevara; Ramiro Aguilar; Maria Gabriela Boaventura; Ricardo Campos; Ek del Val; Guilherme Ramos Demetrio; Marcilio Fagundes; Rafael de Paiva Farias; et al. (Ecology, 2026)
Leaf herbivory is a ubiquitous ecological interaction that varies significantly in intensity across species, habitats, and biogeographic regions. Although quantification of leaf damage is crucial for understanding many ecological processes, the accuracy and precision of various damage estimation methods used by researchers, including visual estimation, digital image analysis, and artificial intelligence, have not been evaluated and compared. We use a phylogenetically diverse group of tropical plants to compare the accuracy and precision of damage estimation methods and use the results to provide a guide to herbivory estimation that balances the advantages and disadvantages of each method. We found that visual estimation tended to overestimate herbivory levels compared to digital methods but was 15 times faster and improved in accuracy and speed with training. Conversely, deep‐learning algorithms underestimated herbivory relative to image analysis with ImageJ when it was on the margin, but showed similar accuracy for damage inside of leaf margins. Our results indicate that while visual methods allow for rapid assessment of large sample sizes and are suitable for detecting broad patterns of damage, image analysis is crucial for accurate and precise quantification. The disadvantages of each method, however, can be minimized through proper training and efficient use of each tool, and we therefore provide a guide of practical approaches to herbivory estimation.

Asymmetries challenging global biodiversity sciences - Leandro O. Salles; Hussam Zaher; Marcos Tavares; Mario C. C. de Pinna; Rosane G. Collevatti; Krister T. Smith; Diego Pol; Hongyu Yi; Nancy B. Simmons; Christopher J. Tribe; Joaquin Arroyo-Cabrales; Nour-Eddine Jalil; et al. (Systematics and Biodiversity, 2026)

Petrogenetic insights of Bezerros and Serra Negra plutons: evidence of syn/post-collisional shoshonitic magmatism in the Caruaru-Arcoverde Batholith, Rio Capibaribe Domain, Northeastern Brazil - Syllas E.S. Santos; Alcides N. Sial; Valderez P. Ferreira; Charles H.F.S. Neves; Bianca T.A. Lima; Diego H. Ardila; Júlio C. Mendes; Cláudia R. Passarelli (Journal of South American Earth Sciences, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Quinolinium-substituted porphyrins as promising antimicrobial photosensitizers - Leticia D. Costa; Cátia Vieira; Mariana Q. Mesquita; Steffen Hackbarth; M. Graça P.M.S. Neves; Adelaide Almeida; Augusto C. Tomé; M. Amparo F. Faustino (Journal of Photochemistry and Photobiology B: Biology, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Immobilization of laccase on grape seed-derived hydrochar and biochar as sustainable biocatalysts for efficient pharmaceutical degradation in real wastewater - Helena Sá; Michele Michelin; Teresa Tavares; Maria Angeles Sanroman; Emilio Rosales; Isabel C. Neves; Bruna Silva (Journal of Environmental Chemical Engineering, 2025)

HIV latency-reversing activity of latex from Euphorbia umbellata (Pax) Bruyns and three diterpenes isolated from this species - Gabrielle P. das Neves; José L. Mazzei; João B. F. Tostes; Marcos J. Nakamura; Helvécio V. A. Rocha; Pedro Junior P. Mourão; Amilcar Tanuri; Antonio J. Ribeiro da Silva; Antonio C. Siani (Natural Product Research, 2025)

A critical analysis of the marina environmental risk assessment method applied to Portugal - Maria C. Neves; Alexandra Cravo; José Jacob; Catia Correia (Regional Studies in Marine Science, 2025)

On the design and stability of cancer adaptive therapy cycles: Deterministic and stochastic models - Yuri G. Vilela; Artur C. Fassoni; Armando G.M. Neves (Mathematical Biosciences, 2025)

Acid-modified titanate nanotubes for enhanced photocatalytic removal of contaminants of emerging concern in water - Guenther Carlos C. Viana; Djalma L.S. Maia; Daniel A.S. Rodrigues; Lara Fabian S. Ribeiro; Italo O. Mazali; Fernando Rodrigues-Silva; Maria Clara V.M. Starling; Thiago A. Neves; Camila C. Amorim (Journal of Water Process Engineering, 2025)

Upregulation of NLRP3 Inflammasome in Specific Hippocampal Regions: Strengthening the Link Between Neuroinflammation and Selective Vulnerability in Alzheimer’s Disease - Eliana C. B. Toscano; Alberto F. O. Justo; Michelle C. A. Paula; Laura B. Grossi; Vitor H. Neves; Renata E. P. Leite; Vitor R. Paes; Rossana C. N. Melo; Ricardo Nitrini; Carlos Pasqualucci; Eduardo Ferriolli; Antonio L. Teixeira; et al. (Molecular Neurobiology, 2025)

Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

Forest Age Rivals Climate to Explain Reproductive Allocation Patterns in Forest Ecosystems Globally - Rachel E. Ward; Huanyuan Zhang‐Zheng; Kate Abernethy; Stephen Adu‐Bredu; Luzmilla Arroyo; Andrew Bailey; Jos Barlow; Erika Berenguer; Liana Chesini‐Rossi; Percival Cho; Cecilia A. L. Dahlsjö; Eder Carvalho das Neves; et al. (Ecology Letters, 2025)
Forest allocation of net primary productivity (NPP) to reproduction (carbon required for flowers, fruits, and seeds) is poorly quantified globally, despite its critical role in forest regeneration and a well‐supported trade‐off with allocation to growth. Here, we present the first global synthesis of a biometric proxy for forest reproductive allocation (RA) across environmental and stand age gradients from a compiled dataset of 824 observations across 393 sites. We find that ecosystem‐scale RA increases ~60% from boreal to tropical forests. Climate shows important non‐linear relationships with RA, but is not the sole predictor. Forest age effects are comparable to climate in magnitude (MAT: ß = 0.24, p = 0.021; old growth forest: ß = 0.22, p p = 0.001; soil N: ß = −0.07, p = 0.001). These results provide strong evidence that ecosystem‐scale RA is mediated by climate, forest age, and soil conditions, and is not a globally fixed fraction of positive NPP as assumed by most vegetation and ecosystem models. Our dataset and findings can be used by modellers to improve predictions of forest regeneration and carbon cycling.

Monitoring the presence of pigments in aqueous extracts using silica materials functionalized with ionic liquids - Gabriela Kovaleski; Márcia C. Neves; Sónia P.M. Ventura (Algal Research, 2025)

Functional characterization of vitellogenin unveils novel roles in RHBP uptake and lifespan regulation in the insect vector Rhodnius prolixus - Jéssica Pereira; Thamara Rios; Juliana Amorim; Allana Faria-Reis; Elisa de Almeida; Matheus Neves; Samara Santos-Araújo; Lukas Selim; Felipe Bertuci; Marcyellen B. Silva; Raquel Onofre; Mellisia Brandão; et al. (Insect Biochemistry and Molecular Biology, 2025)

Neuroinflammation in Severe COVID-19: The Dynamics of Inflammatory and Brain Injury Markers During Hospitalization - Carla Andretta Moreira Neves; Gilson P. Dorneles; Paula C. Teixeira; Paulo C. Santana Filho; Alessandra Peres; Carina Rodrigues Boeck; Liane N. Rotta; Claudia E. Thompson; Pedro R. T. Romão (Molecular Neurobiology, 2025)

Dietary profiles of wild carnivores and Blastocystis occurrence: The case of the endangered Iberian lynx (Lynx pardinus) and systematic review - Javier Caballero-Gómez; Gabriel Ávalos; Pablo Matas-Méndez; Ana M. Figueiredo; Sabrina Castro-Scholten; Débora Jiménez-Martín; Pamela C. Köster; Mónica Santín; Begoña Bailo; David Cano-Terriza; Pedro Sarmento; Nuno Neves; et al. (Research in Veterinary Science, 2025)

Bimetallic-zeolite nanomaterials as catalysts for degradation of azorubine dye via Fenton-like oxidation - Imane El Mrabet; Bebiana L.C. Santos; Karim Tanji; Elisabetta Rombi; Pier Parpot; António M. Fonseca; Hicham Zaitan; Isabel C. Neves (Journal of Water Process Engineering, 2025)

Multistage emplacement of a composite intrusion: magnetic fabric and zircon U–Pb age of the Parnamirim Pluton, NE Brazil - C. H. F. S. Neves; S. P. Neves; V. P. Ferreira; A. N. Sial; B. T. A. Lima; D. H. Ardila; R. Siqueira (International Journal of Earth Sciences, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Analysis of free-living seabirds from Brazil as potential hosts of Toxoplasma gondii and serological investigation for antibodies against Leptospira spp. - Igor C. L. Acosta; Daniela P. Chiebao; Patricia P. Serafini; Gabriel Canani; Hilda F. J. Pena; Marcos B. Heinemann; Antonio F. Souza-Filho; Cynthia Campolina; Caio A. Marques; Tatiana S. Neves; Marcio A. Efe; Guilherme T. Nunes; et al. (Veterinary Research Communications, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Preliminary insight of pollen morphology of the Amazonian members of subtribe Columneineae (Gesneriaceae): details of morphological variation and pollen types - Ana Carolina Venancio Lopes; Cintia Neves de Souza; John L. Clark; Lorrayne Albernaz D. C. Landi; Eduardo Lopes Soares; Isaura de Paula Cerdan; Eduardo Custódio Gasparino (Brazilian Journal of Botany, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Tackling water contamination by oncologic drugs: Supported ionic liquids as sustainable adsorbents for cyclophosphamide removal - Rafael Francisco; Bruna Monteiro; Maria J. Santos; Francisca A. e Silva; Catia Venancio; Marcia C. Neves; Isabel Lopes; Ana C.A. Sousa; Mara G. Freire (Journal of Environmental Management, 2024)

A multicommuted system using bacterial cellulose for urease immobilization and copper (II)-MOF colorimetric sensor for urea spectrophotometric determination in milk - Julyana C. Rodrigues; Caio S. Bezerra; Lidiane M.A. Lima; Danielle D. Neves; Ana Paula S. Paim; Wagner E. Silva; André F. Lavorante (Food Chemistry, 2024)

Patterns and trends of atmospheric mercury in the GMOS network: Insights based on a decade of measurements - Mariantonia Bencardino; Francesco D’Amore; Hélène Angot; Lorenzo Angiuli; Yann Bertrand; Warren Cairns; María C. Diéguez; Aurélien Dommergue; Ralf Ebinghaus; Giulio Esposito; Kateřina Komínková; Casper Labuschagne; et al. (Environmental Pollution, 2024)

Seasonal dynamics of microcystins and microcystin-producing Microcystis populations in three water bodies in Mozambique - Olivia C. N. Pedro; Knut G. Berdal; Elisabeth Lie; Dácia Correia; Luis Neves; Morten Sandvik (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Integrating standardized indices and performance indicators for better drought assessment in semi-arid coastal aquifers - Maria C. Neves (Groundwater for Sustainable Development, 2024)

Construction and demolition waste as a low-cost adsorbent for water treatment: kinetics, isotherm, thermodynamics, and Fenton regeneration - Danilo H. S. Santos; Larissa F. Queiroz; Luiz D. Silva Neto; Keven E. Santos; Denio D. C. S. das Neves; Anamália F. Silva; Eduardo J. S. Fonseca; Daniel P. Fernandes; Lucas Meili (Environmental Science and Pollution Research, 2024)

Plastic use as nesting material can alter incubation temperature and behaviour but does not affect yellow-legged gull chicks - Sara N. Veríssimo; Filipe Veloso; Francisco Neves; Jaime A. Ramos; Vitor H. Paiva; Ana C. Norte (Journal of Thermal Biology, 2024)

Symbiodiniaceae‐Derived Fatty Acids Are Stored Differentially Across Giant Clam Species and Organs - Júlia R. Neves; Satie Taniguchi; Márcia C. Bícego; Paulo Y. G. Sumida; Miguel Mies (Marine Ecology, 2024)
Giant clams are invertebrates that form mutualistic associations with Symbiodiniaceae dinoflagellates. Despite their ecological significance, gaps persist regarding our understanding of their trophic ecology. Specifically, it is unknown whether Symbiodiniaceae‐derived photosynthates are metabolized differently according to species and organ. Therefore, we maintained Tridacna derasa and T. noae for 3 months in a well‐lit recirculated system without food supply. Samples were taken from eight organs and underwent lipid extraction and fatty acid esterification before analysis of three symbiont‐derived fatty acids (stearidonic acid, docosapentaenoic acid, and docosahexaenoic acid—SDA, DPA, and DHA, respectively) using gas chromatography. Results show considerable variation in fatty acids concentration among species and organs. SDA was found in higher concentrations in T. noae , especially in the adductor muscle. DPA was detected in low concentrations across T. noae organs and absent for T. derasa . DHA did not vary significantly among species and organs. Our findings indicate that Symbiodiniaceae supply clams with fatty acids, which are stored differentially according to species and organs. This demonstrates that these compounds are translocated to multiple organs throughout the complex giant clam anatomical system, in contrast to simpler hosts like corals. These results advance our understanding of the physiological dynamics of the mollusk‐algae association.

Stratigraphic-chemostratigraphic assessment of early dolomitization and associated phosphogenesis of the Ediacaran-Cambrian Salitre Formation, Irecê Basin, Brazil - C. Bedoya-Rueda; J. Afonso; S. Caetano-Filho; G. Paula-Santos; C. Guacaneme; P. Fraga-Ferreira; M. Babinski; K. Amorim; L. Morais; B. Brito Neves; R. Trindade (Precambrian Research, 2024)

Kinin B1 receptor deficiency promotes enhanced adipose tissue thermogenic response to β3-adrenergic stimulation - Jéssica Branquinho; Raquel L. Neves; Renan P. Martin; Júlia G. Arata; Clarissa A. Bittencourt; Ronaldo C. Araújo; Marcelo Y. Icimoto; João B. Pesquero (Inflammation Research, 2024)

Efficient photocatalytic degradation of diclofenac drug using the Zn1-x-yPrxAlyO photocatalyst under UV light irradiation - Emanoel Martins; Pollyana Trigueiro; Aimée G. Jerônimo; Ricardo Barbosa; Luan Neves; Débora A. Sales; Luciano C. Almeida; Bartolomeu C. Viana; Adriano S. Soares; Ramón R. Peña-Garcia (Environmental Science and Pollution Research, 2024)

A biofloc system avoids the adverse effects of diets with suboptimal protein levels on zootechnical performance, intestinal histomorphometry, and protein metabolism of Nile tilapia juvenile fed Spirulina biomass (Arthrospira platensis) as an alternative protein source - Fernanda Picoli; Alana D. de Oliveira; Suelyn O. Marques; Deise C. Terhorst; Suélen Serafini; Luísa Nora; Fabio F. Neves; Maurício G. C. Emerenciano; Diogo L. A. Lopes; Aleksandro S. da Silva; Thiago E. H. P. Fabregat (Fish Physiology and Biochemistry, 2024)

Beta diversity and regionalization of the western Atlantic marine biota - Ubirajara Oliveira; Fernanda Azevedo; Alan Dias; Ana Carolina Sousa de Almeida; André R. Senna; Antonio C. Marques; Dafinny Rezende; Eduardo Hajdu; Erick Alves Pereira Lopes‐Filho; Fábio Bettini Pitombo; Gabriela Moura de Oliveira; João Gabriel Doria; et al. (Journal of Biogeography, 2024)
Aim Understanding the factors determining marine community variations is important for biogeography and conservation. Beta diversity is a metric for mapping species composition variations between communities and regionalizing biota. Ecoregions are commonly used for regionalization, but their empirical testing has been limited. Our aim is to map marine species composition variations in the Western Atlantic, identify variables related to these variations, and regionalize areas based on community distribution. Additionally, we test whether currently proposed ecoregions represent unique biota units and specific environmental conditions. Location Western Atlantic Ocean. Taxon Vertebrates, invertebrates and algae. Methods We constructed a large marine biodiversity database, including vertebrates, invertebrates, and algae, totalling over 4 million records. We used the generalized dissimilarity model (GDM) to identify variables most related to species composition variations and map beta‐diversity variations. We employed an unsupervised classifier for community regionalization. To test if the ecoregion regionalization boundaries are corroborated by species distribution data, we used the Sørensen index. To assess if ecoregions correspond to environmental units, we checked if areas had distinct environmental conditions using a PCA of 134 marine environmental variables. Results The GDM explained a high variation in species composition, 61% in the complete database. Analysing vertebrates, invertebrates and algae separately also yielded relatively high results: 46%, 54%, and 33%, respectively. Coastal areas differed from open sea areas in composition. Environmental variables combined better explained beta diversity than isolated variables. The regionalization based on GDM was not congruent with ecoregion boundaries. Moreover, ecoregions showed no distinction in species composition or environmental conditions. Main Conclusions This study's regionalization is crucial for marine biodiversity conservation, focusing on understanding species composition patterns between coastal and open sea areas to develop tailored conservation strategies. Despite sampling limitations, the study advances marine biogeography knowledge by analysing over 4 million species records and 134 environmental variables. This comprehensive approach enhances understanding marine species distribution and diversity and aiding the development of effective conservation measures.

Land use intensification has extensive effects on the functional and phylogenetic diversity of neotropical ant communities - Heraldo L. Vasconcelos; Karen C. Neves; Jésica Vieira; Raquel L. Carvalho (Biodiversity and Conservation, 2024)

Anatomy of the olfactory system and potential role for chemical communication in the sound‐producing Lusitanian toadfish, Halobatrachus didactylus - Teresa Modesto; Beatriz Neves Gregório; Gonçalo Marcelino; Nathalie Marquet; Rita A. Costa; Pedro M. Guerreiro; Zélia Velez; Peter C. Hubbard (Journal of Fish Biology, 2024)
The current study investigated the structure and function of the olfactory system of the Lusitanian toadfish, Halobatrachus didactylus , using histology and electrophysiology (electro‐olfactogram [EOG]), respectively. The olfactory system consists of a digitated anterior peduncle, of unknown function, containing the inhalant nostril. This then leads to a U‐shaped olfactory chamber with the olfactory epithelium—identified by G αolf ‐immunoreactivity—on the ventral surface. A large lacrimal sac is connected to this tube and is likely involved in generating water movement through the olfactory chamber (this species is largely sedentary). The exhalent nostril lies by the eye and is preceded by a bicuspid valve to ensure one‐way flow of water. As do other teleosts, H. didactylus had olfactory sensitivity to amino acids and bile acids. Large‐amplitude EOG responses were evoked by fluid from the anterior and posterior testicular accessory glands, and bile and intestinal fluids. Anterior gland and intestinal fluids from reproductive males were significantly more potent than those from non‐reproductive males. Male urine and skin mucus proved to be the least potent body fluids tested. These results suggest that chemical communication—as well as acoustic communication—may be important in the reproduction of this species and that this may be mediated by the accessory glands and intestinal fluid.

Evidence of plastics contamination and sewage-derived residues in a Brazilian Hope Spot for conservation of marine biodiversity - Cagarras Islands and surrounding waters - Raquel A.F. Neves; Nathália Rodrigues; Guilherme de Luca; Maria Alene A. Oliveira; Thuany F. Carvalho; Nicole S. Santos; Maria Eduarda S. Adelino; Luiza Belli Caldas; Agatha Miralha; Clarissa Naveira; Antonio J.S. Rodrigues; Igor C. Miyahira; et al. (Marine Pollution Bulletin, 2024)

Extraction of platinum and palladium from aqueous solutions using ionic-liquid-modified magnetic nanoparticles - Joana C. Almeida; Celso E.D. Cardoso; Márcia C. Neves; Tito Trindade; Mara G. Freire; Eduarda Pereira (Journal of Water Process Engineering, 2024)

Congenital right atrial diverticulum in a kitten - B. Pedro; F. Sarcinella; C. Linney; J. Neves; L. Mesquita (Journal of Veterinary Cardiology, 2024)

Filling gaps in the Webbnesia marine diversity: The madeiran sponge fauna - A. Santín; P. Wirtz; P. Neves; C. Ribeiro (Continental Shelf Research, 2024)

The cost of genetic diagnosis of suspected hereditary pediatric cataracts with whole-exome sequencing from a middle-income country perspective: a mixed costing analysis - Luiza M. Neves; Márcia Pinto; Olivia A. Zin; Daniela P. Cunha; Bruna N. S. Agonigi; Fabiana L. Motta; Leonardo H. F. Gomes; Dafne D. G. Horovitz; Daltro C. Almeida; Jocieli Malacarne; Leticia Guida; Andressa Braga; et al. (Journal of Community Genetics, 2024)
Up to 25% of pediatric cataract cases are inherited. There is sparse information in the literature regarding the cost of whole-exome sequencing (WES) for suspected hereditary pediatric cataracts. Molecular diagnosis of suspected hereditary pediatric cataracts is important for comprehensive genetic counseling. We performed a partial economic evaluation with a mixed costing analysis, using reimbursement data and microcosting approach with a bottom-up technique to estimate the cost of using WES for genetic diagnosis of suspected hereditary pediatric cataracts from the perspective of the Brazilian governmental health care system. One hundred and ten participants from twenty-nine families in Rio de Janeiro (RJ) were included. Costs of consumables, staff and equipment were calculated. Two scenarios were created: (1) The reference scenario included patients from RJ with suspected hereditary pediatric cataracts plus two family members. (2) The alternative scenario considered other genetic diseases, resulting in 5,280 exams per month. Sensitivity analysis was also performed. In the reference scenario, the total cost per exam was 700.09 United States dollars (USD), and in the alternative scenario, the total cost was 559.23 USD. The cost of WES alone was 527.85 USD in the reference scenario and 386.98 USD in the alternative scenario. Sensitivity analysis revealed that the largest costs were associated with consumables in both scenarios. Economic evaluations can help inform policy decisions, especially in middle-income countries such as Brazil.

Fatal interactions of albatrosses with weather radiosondes/balloons on the Southern and Southeastern coasts of Brazil - D.W. Goldberg; C. Sardinha; D.E. Oliveira; P.V. Castilho; J.V. Vieira; J. Ikeda; C.A. Marques; T.S. Neves; G. Canani (Marine Pollution Bulletin, 2024)

Is a recent large expansion of a no-take reserve sufficient to change the reef fish assemblage? A before-after assessment in Alcatrazes Wildlife Refuge, Southwestern Atlantic - Fernanda A. Rolim; Fernando Z. Gibran; Leonardo M. Neves; Natalia C. Roos; Guilherme H. Pereira-Filho; Gabriel R. Souza; Domingos Garrone-Neto; Fabio S. Motta (Ocean & Coastal Management, 2024)

How do microplastics alter molluscicidal activity? Effects of weathered microplastics and niclosamide in developing freshwater snails - Cândido C. Rodrigues; Cyntia A.Y. Harayashiki; Eufrásia S. Pereira; Gabriel L.S. Rodrigues; Bruno J. Neves; Thiago L. Rocha (Science of The Total Environment, 2024)

Microplastics and TiO2 nanoparticles mixture as an emerging threat to amphibians: A case study on bullfrog embryos - Raquel Fernanda Salla; Fagner Neves Oliveira; Jaqueline C. Jacintho; Felipe Cirqueira; Elisabete Tsukada; Lucélia Gonçalves Vieira; Thiago Lopes Rocha (Environmental Pollution, 2024)

Sustainability in reverse osmosis membranes waste management: Environmental and socioeconomic assessment - Luiza B. Grossi; Eric F.O. Neves; Liséte C. Lange; Míriam C.S. Amaral (Desalination, 2024)

Effects of invasive sun corals on habitat structural complexity mediate reef trophic pathways - Lucas S. Neves da Rocha; José Anchieta C. C. Nunes; Ricardo J. Miranda; Ruy K. P. Kikuchi (Marine Biology, 2024)

Spatiotemporal distribution of invertebrate fauna in a mesovoid shallow substratum in iron formations - Lígia Maria Saback Moreira Dornellas; Pedro Giovâni da Silva; Maria Elina Bichuette; Augusto S. Auler; David C. Culver; Tanja Pipan; Lorena Oliveira Pires; Frederico de Siqueira Neves (Biodiversity and Conservation, 2024)

A new understanding of somatic coliphages belonging to the Microviridae family in urban wastewater - Marion C. Bichet; Marion Gardette; Benjamin Das Neves; Julie Challant; Anaïs Erbs; Véronica Roman; Maëlle Robin; Stéphanie La Carbona; Christophe Gantzer; Nicolas Boudaud; Isabelle Bertrand (Water Research, 2024)

Molecular Verification of Trichophyton in the Brazilian URM Culture Collection - Tatiana F. Oliveira; Carlos A. T. Valeriano; M. Daniela S. Buonafina-Paz; Cristina M. Souza-Motta; Alexandre R. Machado; Rejane P. Neves; Jadson D. P. Bezerra; Thales D. Arantes; Sybren de Hoog; Oliane M. C. Magalhães (Mycopathologia, 2024)

Application of a tannin-based coagulant for harvesting Parachlorella kessleri microalgae cultivated in chicken meat thermal processing wastewater - Luana Búrigo Vargas; Thais Agda R. da C. Primo; Rafaela Dexcheimer Alves; Fabio de Farias Neves; Viviane Trevisan; Everton Skoronski (Aquaculture International, 2024)

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Valorization of plant by-products in the biosynthesis of silver nanoparticles with antimicrobial and catalytic properties - Verónica Rocha; Pedro Ferreira-Santos; Cristina Aguiar; Isabel C. Neves; Teresa Tavares (Environmental Science and Pollution Research, 2024)
Biosynthesis based on natural compounds has emerged as a sustainable approach for the production of metallic nanoparticles (MNP). The main objective of this study was to biosynthesize stable and multifunctional silver nanoparticles (AgNP) using different plant by-products as reducers and capping agents. Extracts obtained from Eucalyptus globulus , Pinus pinaster, Citrus sinensis , Cedrus atlantica and Camellia sinensis by-products, were evaluated. From all plant by-products tested, aqueous extract of eucalyptus leaves (EL), green tea (GT) and black tea (BT) were selected due to their higher antioxidant phenolic content and were individually employed as reducers and capping agents to biosynthesize AgNP. The green AgNP showed zeta potential values of -31.8 to -36.3 mV, with a wide range of particle sizes (40.6 to 86.4 nm), depending on the plant extract used. Green AgNP exhibited an inhibitory effect against various pathogenic bacteria, including Gram-negative ( P. putida, E. coli , Vibrio spp. ) and Gram-positive ( B. megaterium, S. aureus, S. equisimilis ) bacteria with EL-AgNP being the nanostructure with the greatest antimicrobial action. EL-AgNP showed an excellent photodegradation of indigo carmine (IC) dye under direct sunlight, with a removal percentage of up to 100% after 75 min. A complete cost analysis revealed a competitive total cost range of 8.0–9.0 €/g for the biosynthesis of AgNP. Graphical Abstract

Distributions and sources of bulk organic matter from surface sediments along the Southwestern Atlantic Margin - Lígia D. Araujo; Felipe S. Freitas; Felipe R. Santos; Satie Taniguchi; Cristian T. Timoszczuk; Leticia Burone; Rafael A. Lourenço; Patricia A. Neves; Matilde Rodríguez; Michel M. de Mahiques; Márcia C. Bícego (Journal of South American Earth Sciences, 2024)

Antimicrobial Resistance Profiles of Multidrug-Resistant Enterobacteria Isolated from Feces of Weaned Piglets - Marlon do Valle Barroso; Juliana Soares da Silva; Sofia Magalhães Moreira; Yasmin Neves Vieira Sabino; Gabriel Cipriano Rocha; Maria Aparecida Scatamburlo Moreira; Denise Mara Soares Bazzolli; Hilario C. Mantovani (Current Microbiology, 2024)

Spatial and temporal abilities of proxies used to detect pre-Columbian Indigenous human activity in Amazonian ecosystems - C.N.H. McMichael; C. Levis; W.D. Gosling; A.B. Junqueira; D.R. Piperno; E.G. Neves; F. Mayle; M. Peña-Claros; F. Bongers (Quaternary Science Reviews, 2023)

Environmental remediation promoted by silver nanoparticles biosynthesized by eucalyptus leaves extract - Verónica Rocha; Pedro Ferreira-Santos; Zlatina Genisheva; Eduardo Coelho; Isabel C. Neves; Teresa Tavares (Journal of Water Process Engineering, 2023)

A new Loriciferan, Scaberiloricus samba gen. et sp. nov., links the Higgins larva and the aberrant Shira larva - Martin V. Sørensen; Maria Herranz; Ricardo C. Neves; Reinhardt M. Kristensen; André R. S. Garraffoni (Organisms Diversity & Evolution, 2023)
A new genus and species of Loricifera, Scaberiloricus samba gen. et sp. nov., is described from the continental shelf and slope off Rio de Janeiro, Brazil. Adult morphology remains unknown for the new entity, but information is available from three different Higgins larval instars. The Higgins larva of the new species is characterised by a bulbous head and a slender, elongate trunk, separated by a constriction behind the head. The cuticle of the thorax and the posterior part of the head is characterised by numerous longitudinal zigzag folds. The new species and genus shows greatest morphological resemblance with Wataloricus japonicus , and a phylogenetic analysis based on Higgins larval morphological characters suggests that Scaberiloricus gen. nov., Wataloricus , Tenuiloricus , and Patuloricus form a monophyletic group within Pliciloricidae. The analysis furthermore suggests that the Higgins larvae of Scaberiloricus gen. nov. and Wataloricus represent transitional, evolutionary stages towards the highly aberrant Shira larvae, found in species of Tenuiloricus and Patuloricus .

1,4-Diaryl-1,2,3-triazole neolignan–celecoxib hybrids inhibit experimental arthritis induced by zymosan - Josyelen L. Felipe; Iluska S. Bonfá; Paloma K. M. B. Lossavaro; Joyce S. Lencina; Diego B. Carvalho; Luciane Candeloro; Giovanni I. S. Ferreira; Amarith R. das Neves; Maria Inês L. Souza; Saulo E. Silva-Filho; Adriano C. M. Baroni; Mônica C. Toffoli-Kadri (Inflammopharmacology, 2023)

Isolation drives species gains and losses of insect metacommunities over time in a mountaintop forest archipelago - Pedro Giovâni da Silva; Marina do Vale Beirão; Flávio Siqueira de Castro; Lucas Neves Perillo; Flávio Camarota; Ricardo R. C. Solar; Geraldo Wilson Fernandes; Frederico de Siqueira Neves (Journal of Biogeography, 2023)
Aim We evaluated the effects of forest island size, isolation and area in the landscape driving temporal changes of insect biodiversity in a mountaintop forest archipelago. We expected that (i) in smaller, less isolated forest islands, changes in insect composition are more prominent, primarily driven by gains over time; (ii) more forest in the landscape leads to increased gains of vagile species over time, regardless of forest island size and isolation; (iii) less vagile groups undergo heterogenisation, while highly vagile groups experience homogenisation due to differing dispersal capabilities. Location Espinhaço Range Biosphere Reserve, Brazil. Taxon Insects. Methods We used ants, dung beetles, bees, wasps and butterflies as study models to represent a gradient of low‐to‐high dispersal capability. We evaluated the colonisation‐ and extirpation‐resultant components of temporal β‐diversity using area‐ and isolation‐related variables as predictors. Results Distinct colonisation‐ and extirpation‐resultant homogenisation and heterogenisation processes are acting according to each insect group, likely due to different dispersal capabilities. Species losses dominated in ants, with widespread and rare species being lost. Butterflies gained species, represented mainly by widespread species, leading to an increased colonisation‐resultant homogenisation. Distance to neighbouring forest islands was the underlying predictor affecting the temporal β‐diversity of insect groups, and also species gains and losses but differently according to the survey period. Effects of the forest amount in the landscape increased the temporal β‐diversity of bees and butterflies but decreased that of ants, dung beetles and wasps. Main Conclusions These findings provide valuable biogeographic insights into the complex interactions between forest island characteristics, landscape attributes, and dispersal capabilities that shape the temporal dynamics of insect biodiversity on mountaintops. Conserving the forest amount in the landscape and keeping forest connectivity among forest islands are necessary because the temporal dynamics of local colonisation and extirpation can depend on the organisms' dispersal capability.

Versatile click alginate hydrogels with protease-sensitive domains as cell responsive/instructive 3D microenvironments - Mariana I. Neves; Mariana V. Magalhães; Sílvia J. Bidarra; Lorenzo Moroni; Cristina C. Barrias (Carbohydrate Polymers, 2023)

From pioneers to modern-day taxonomists: the good, the bad, and the idiosyncrasies in choosing species epithets of rotifers and microcrustaceans - Rafael L. Macêdo; Lourdes M. A. Elmoor-Loureiro; Francisco Diogo R. Sousa; Arnola C. Rietzler; Gilmar Perbiche-Neves; Odete Rocha (Hydrobiologia, 2023)

Optimization of iron-ZIF-8 catalysts for degradation of tartrazine in water by Fenton-like reaction - Ouissal Assila; Natália Vilaça; Ana R. Bertão; António M. Fonseca; Pier Parpot; Olívia S.G. P. Soares; Manuel F.R. Pereira; Fátima Baltazar; Manuel Bañobre-López; Isabel C. Neves (Chemosphere, 2023)

Sustainable fluorescent dye-faujasite zeolite systems as tools for cancer bioimaging - Ana R. Bertão; Orhan Güney; Marta Costa; Patrícia Fontão; Olga Martinho; Susana P.G. Costa; António M. Fonseca; Olívia S.G.P. Soares; Manuel Bañobre-López; Fátima Baltazar; Isabel C. Neves (Chemical Engineering Journal, 2023)

Alkylamides from Acmella oleracea : antinociceptive effect and molecular docking with cannabinoid and TRPV1 receptors - Raíssa M. Kao Yien; Anne Caroline C. Gomes; Rodolfo Goetze Fiorot; Ana Luísa Palhares Miranda; Gilda A. Neves; Brenda da Silva Andrade; Fernanda N. Costa; Jorge Luiz Mendonça Tributino; Naomi Kato Simas (Natural Product Research, 2023)

Levelling-up rhodolith-bed science to address global-scale conservation challenges - Fernando Tuya; Nadine Schubert; Julio Aguirre; Daniela Basso; Eduardo O. Bastos; Flávio Berchez; Angelo F. Bernardino; Néstor E. Bosch; Heidi L. Burdett; Fernando Espino; Cindy Fernández-Gárcia; Ronaldo B. Francini-Filho; et al. (Science of The Total Environment, 2023)

First Report of a Wastewater Treatment-Adapted Enterococcus faecalis ST21 Harboring vanA Gene in Brazil - Beatriz O. Farias; Kaylanne S. Montenegro; Ana Paula A. Nascimento; Mariana Magaldi; Andressa S. Gonçalves-Brito; Claudia Flores; Thais C. Moreira; Felipe P. G. Neves; Kayo Bianco; Maysa M. Clementino (Current Microbiology, 2023)

Removal of mercury by silica-supported ionic liquids: Efficiency and ecotoxicological assessment - Thainara Viana; Raquel Almeida; Paula Figueira; Luciana Rocha; Márcia C. Neves; Rosa Freitas; Mara Freire; Bruno Henriques; Eduarda Pereira (Aquatic Toxicology, 2023)

Vertical stratification of ant assemblages varies along a latitudinal gradient in Brazilian savanna - Heraldo L. Vasconcelos; Karen C. Neves; Alan N. Andersen (Journal of Biogeography, 2023)
Aim Arboreal and ground‐dwelling species experience distinct microclimates, have contrasting thermal tolerances and thus may be expected to respond differentially to geographic climatic gradients. We tested this idea by evaluating if the degree of vertical stratification of savanna ant assemblages varies along a latitudinal climatic gradient, and by determining how compositional dissimilarities within each stratum varies across increased geographical and climatic distances. Location Brazil. Taxon Ants. Methods We sampled ants foraging on the ground or in trees at 32 sites. Species were classified according to their main foraging stratum, as arboreal, ground‐dweller or strata generalist. We used linear models to evaluate the effects of latitude and sampling stratum on species richness, and the effect of latitude on the proportion of species typical from trees or from the ground in different sampling strata. The influence of geographic and climatic distances on the compositional differences between assemblages from the same stratum was assessed using regression on distance matrices. Results Species richness on the ground increased with latitude significantly faster than in trees. The turnover of species between strata was lower at lower latitudes, where there were proportionally more strata generalists and species typical from the ground stratum foraging in trees. Consequently, the compositional dissimilarity between vertical strata decreased with decreasing latitude. Despite that, the dissimilarities between vertical strata were, on average, as great or even greater than the dissimilarities between assemblages from the same stratum across the horizontal space. Main Conclusions We found support for the idea that climatic variation across latitude had different effects on arboreal compared with ground‐foraging assemblages. Overall, our results suggest that as Brazilian savanna becomes hotter and drier as forecast under climate change, ant assemblages may become not only less diverse, notably on the ground, but also more homogeneous vertically.

Prevalence and Risk Factors Associated With Natural Infection by Trypanosoma evansi in Campeiro Horses - Lisiane Golombieski; Gabriela Bassi das Neves; Mariana da Silva Casa; Gabriela Campos de Souza Costa; Luiz C. Miletti; Mere E. Saito; Joandes H. Fonteque (Journal of Equine Veterinary Science, 2023)

SDS-induced hexameric oligomerization of myotoxin-II from Bothrops asper assessed by sedimentation velocity and nuclear magnetic resonance - Amy Henrickson; Tony Montina; Paul Hazendonk; Bruno Lomonte; Ana Gisele C. Neves-Ferreira; Borries Demeler (European Biophysics Journal, 2023)

Gold nanoparticle intratesticular injections as a potential animal sterilization tool: Long-term reproductive and toxicological implications - John L.P. Coimbra; Graziela de P.F. Dantas; Lídia M. de Andrade; Marcos.R.G. Brener; Pedro I.M. Viana; Roberta.A. Lopes; Daniele. O.G Gontijo; Luiz.O.G. Ervilha; Mirian.Q. Assis; Luciola.S. Barcelos; Raphael. E. Szawka; Débora C. Damasceno; et al. (Toxicology, 2023)

Evaluation of different platelet-rich plasma protocols for use in the equine reproductive clinic - Joel N De Oliveira; Henrique Ba Bastos; Veronica LC Bueno; Gustavo R Larentis; Rodrigo C Mattos; Adriana P Neves (Journal of Equine Veterinary Science, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Geochemical behavior of rare earth elements (REE) in urban reservoirs: the case of Funil Reservoir, Rio de Janeiro State, Brazil - J. M. C. O. Santos-Neves; S. R. Patchineelam; D. F. Araujo; J. M. O. Godoy; A. C. Almeida (Environmental Monitoring and Assessment, 2023)

Multi-center Integrating Radiomics, Structured Reports, and Machine Learning Algorithms for Assisted Classification of COVID-19 in Lung Computed Tomography - Marcos A. D. Machado; Ronnyldo R. E. Silva; Mauro Namias; Andreia S. Lessa; Margarida C. L. C. Neves; Carolina T. A. Silva; Danillo M. Oliveira; Thamiris R. Reina; Arquimedes A. B. Lira; Leandro M. Almeida; Cleber Zanchettin; Eduardo M. Netto (Journal of Medical and Biological Engineering, 2023)

Levels and sources of hydrocarbons in the Patos Lagoon estuary and Cassino Beach mud bank (South Atlantic, Brazil): evidence of transference between environments - Patricia Andrade Neves; Patricia G. Costa; Luana C. Portz; Marina R. Garcia; Gilberto Fillmann (Environmental Monitoring and Assessment, 2023)

The signature of NAO and EA climate patterns on the vertical structure of the Canary Current upwelling system - Tina Georg; Maria C. Neves; Paulo Relvas (Ocean Science, 2023)
The current study aims to analyse the vertical structure of the ocean during upwelling events using in situ and modelled data. Additionally, the influence of climate patterns, namely the North Atlantic Oscillation (NAO) and the East Atlantic (EA) pattern, on the vertical structure and their impact on the upwelling activity are assessed for a period of 25 years (1993–2017). The study focuses on the central part of the Canary Current (25–35∘ N) with persistent upwelling throughout the year, with an annual cycle and the strongest events from June to September. Upwelling is determined using two different approaches: one index is calculated based on temperature differences between the coastal and the offshore area, and the other is calculated based on wind data and the resulting Ekman transport. Different datasets were chosen according to the indices. Stable coastal upwelling can be observed in the study area for the analysed time span, with differences throughout the latitudes. A deepening of the isothermal layer depth and a cooling of temperatures are observed in the vertical structure of coastal waters, representing a deeper mixing of the ocean and the rise of cooler, denser water towards the surface. During years of a positive NAO, corresponding to a strengthening of the Azores High and the Icelandic Low, stronger winds lead to an intensification of the upwelling activity, an enhanced mixing of the upper ocean, and a deeper (shallower) isothermal layer along the coast (offshore). The opposite is observed in years of negative NAO. Both effects are enhanced in years with a coupled, opposite phase of the EA pattern and are mainly visible during winter months, where the effect of both indices is the greatest. The study therefore suggests that upwelling activities are stronger in winters of positive North Atlantic Oscillation coupled with a negative East Atlantic pattern and emphasizes the importance of interactions between the climate patterns and upwelling.

Hypereutrophic conditions limit the removal of suspended particulate matter by the invasive bivalve Mytilopsis leucophaeata (Conrad, 1831) (Dreissenidae) - Nathália Rodrigues; Danielle Ribeiro; Igor C. Miyahira; Samira G. M. Portugal; Luciano N. Santos; Raquel A. F. Neves (Hydrobiologia, 2023)

Evidence of earthquake seasonality in the Azores Triple Junction - Ana L. Lordi; Maria C. Neves; Susana Custódio; Stéphanie Dumont (Geo-Marine Letters, 2023)
This work presents evidence of seasonal and inter-annual variations of the earthquake occurrence rate in the Azores Triple Junction, on the Mid-Atlantic Ridge (MAR). Annual cycles in microearthquakes are relatively common in intraplate continental regions affected by large hydrological loads, but this is the first time that earthquake seasonality is recognized near mid-ocean ridges. First, we benchmark the methodology by matching the published results of earthquake seasonality in the intraplate New Madrid Seismic Zone (USA). Next, we analyze the Azores earthquake catalogue, from 2008 to 2018, separately for oceanic and island regions. The results demonstrate that the seasonal modulation of the seismicity rate is only observed in the ocean, especially in the vicinity of the triple junction, with more earthquakes occurring during the summer months from May to August. Monte Carlo simulations show that the probability of observing such seasonality by chance is less than 1% for the magnitude band from 3.3 to 4.5, well above the detection threshold and magnitude of completeness of the seismic catalogue. The methodology includes a Jack-Knife approach, which shows that the oceanic seasonality is not the consequence of abnormal or extreme events. Although we speculate about possible earthquake triggering processes, it remains a challenge to definitely establish the mechanism responsible for the observed earthquake seasonal modulation in the Azores.

Granulated biomass fly ash coupled with fenton process for pulp and paper wastewater treatment - João Peres Ribeiro; Nuno C. Cruz; Márcia C. Neves; Sónia M. Rodrigues; Luís A.C. Tarelho; Maria Isabel Nunes (Environmental Pollution, 2023)

Impacts of the use of biological pest control on the technical efficiency of the Brazilian agricultural sector - L. C. C. Rodrigues; R. M. Fortini; M. C. R. Neves (International Journal of Environmental Science and Technology, 2023)

Crossing the Atlantic: The tropical macroalga Caulerpa ashmeadii Harvey 1858 as a recent settler in Porto Santo Island (Madeira archipelago, North-eastern Atlantic) - C. Ribeiro; T. Sauvage; S. Ferreira; R. Haroun; J. Silva; P. Neves (Aquatic Botany, 2023)

Seagrasses benefit from mild anthropogenic nutrient additions - Vasco M. N. C. S. Vieira; Jorge Lobo-Arteaga; Rafael Santos; David Leitão-Silva; Arthur Veronez; Joana M. Neves; Marta Nogueira; Joel C. Creed; Chiara M. Bertelli; Jimena Samper-Villarreal; Mats R. S. Pettersen (Frontiers in Marine Science, 2022)
Seagrasses are declining globally, in large part due to increased anthropogenic coastal nutrient loads that enhance smothering by macroalgae, attenuate light, and are toxic when in excessive concentrations of inorganic nitrogen and phosphorus. However, as sanitation is improved many seagrass meadows have been observed to recover, with a few studies suggesting that they may even benefit from mild anthropogenic nutrient additions. Monitoring seagrass demography and health has faced difficulties in establishing the adequate variables and metrics. Such uncertainty in the methods has caused uncertainty of the significance of results presented and compromised extrapolations to other seasons, areas, or species. One solution has come from within the plant self-thinning theories. During the 1980s, an interspecific boundary line (IBL) was determined as the upper limit of the combination of plant density and above-ground biomass for any stand on Earth, setting their maximum possible efficiency in space occupation. Recently, two meta-analyses to determine specific IBLs for algae and for seagrasses have been performed. The recently updated seagrass dataset comprises 5,052 observations from 78 studies on 18 species. These IBLs opened new perspectives for monitoring: the observed distance of a stand to the respective IBL (i.e., each stand’s relative efficiency of space occupation) was demonstrated to be a valuable indicator of a population’s health. Thus, this metric can be used to determine the impact of nutrients and pollutants on algae and seagrass populations. Furthermore, because the IBLs are common to all species, they may be used to compare all species from any location worldwide. This novel approach showed that Halodule wrightii , Halodule beaudettei , Halophila baillonii , Zostera marina , and Zostera noltei meadows benefit from anthropogenic additions of nitrogen and phosphorus, as long as these additions are moderate. In fact, the healthier Z. noltei meadows in Portugal (and among the healthiest meadows worldwide) were the ones exposed to effluents from wastewater treatment plants (WWTP) and a food factory. We conclude that those effluents are providing water with enough quality and that their optimal management should coordinate the technological solutions of the WWTP with the natural potential of seagrass meadows as water purifiers and biomass producers.

Numerical Model of Constrained Wave Energy Hyperbaric Converter under Full-Scale Sea Wave Conditions - Moisés Brito; Francisco Bernardo; Maria G. Neves; Diogo R. C. B. Neves; Alejandro J. C. Crespo; José M. Domínguez (Journal of Marine Science and Engineering, 2022)
A 2D numerical investigation of the power absorption of a constrained wave energy hyperbaric converter (WEHC) under full-scale sea wave conditions is presented. A fully non-linear numerical model DualSPHysics, based on the coupling of a smoothed particle hydrodynamics (SPH) fluid solver with a multibody dynamics solver, is used to model the interaction between wave and WEHC sub-systems. The numerical model was first validated against experimental data for a similar device, with a good accordance between PTO position and velocity. The model is then employed to study the hydrodynamics of a constrained WEHC considering several sea states, different hydraulic power take-off (PTO) damping and breakwater geometries. It is observed that the capture width ratio (CWR) is particularly sensitive to variations in the PTO damping, although the CWR absolute maximum is less sensitive considering mild variations applied to the PTO damping. Both wave height and wave period have an important effect on the CWR. The breakwater geometry is also essential for the performance of the WEHC, with a decrease in maximum CWR of about 15% for porous breakwater. These results are necessary to understand the full-scale behaviour of WEHC.

Structural analysis of the peptides temporin-Ra and temporin-Rb and interactions with model membranes - José L. S. Lopes; Caio C. F. Araujo; Rogério C. Neves; Jochen Bürck; Sheila G. Couto (European Biophysics Journal, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Wide tolerance to environmental conditions and substrate colonization mediates the invasion of false mussels (Bivalvia: Dreissenidae) in brackish systems - Antonio J. S. Rodrigues; Igor C. Miyahira; Nathália Rodrigues; Danielle Ribeiro; Luciano N. Santos; Raquel A. F. Neves (Biological Invasions, 2022)

A review of the heterogeneous landscape of biodiversity databases: Opportunities and challenges for a synthesized biodiversity knowledge base - Xiao Feng; Brian J. Enquist; Daniel S. Park; Brad Boyle; David D. Breshears; Rachael V. Gallagher; Aaron Lien; Erica A. Newman; Joseph R. Burger; Brian S. Maitner; Cory Merow; Yaoqi Li; et al. (Global Ecology and Biogeography, 2022)
Aim Addressing global environmental challenges requires access to biodiversity data across wide spatial, temporal and taxonomic scales. Availability of such data has increased exponentially recently with the proliferation of biodiversity databases. However, heterogeneous coverage, protocols, and standards have hampered integration among these databases. To stimulate the next stage of data integration, here we present a synthesis of major databases, and investigate (a) how the coverage of databases varies across taxonomy, space, and record type; (b) what degree of integration is present among databases; (c) how integration of databases can increase biodiversity knowledge; and (d) the barriers to database integration. Location Global. Time period Contemporary. Major taxa studied Plants and vertebrates. Methods We reviewed 12 established biodiversity databases that mainly focus on geographic distributions and functional traits at global scale. We synthesized information from these databases to assess the status of their integration and major knowledge gaps and barriers to full integration. We estimated how improved integration can increase the data coverage for terrestrial plants and vertebrates. Results Every database reviewed had a unique focus of data coverage. Exchanges of biodiversity information were common among databases, although not always clearly documented. Functional trait databases were more isolated than those pertaining to species distributions. Variation and potential incompatibility of taxonomic systems used by different databases posed a major barrier to data integration. We found that integration of distribution databases could lead to increased taxonomic coverage that corresponds to 23 years’ advancement in data accumulation, and improvement in taxonomic coverage could be as high as 22.4% for trait databases. Main conclusions Rapid increases in biodiversity knowledge can be achieved through the integration of databases, providing the data necessary to address critical environmental challenges. Full integration across databases will require tackling the major impediments to data integration: taxonomic incompatibility, lags in data exchange, barriers to effective data synchronization, and isolation of individual initiatives.

Rhodolith Physiology Across the Atlantic: Towards a Better Mechanistic Understanding of Intra- and Interspecific Differences - Nadine Schubert; Viviana Peña; Vinícius W. Salazar; Paulo A. Horta; Pedro Neves; Cláudia Ribeiro; Francisco Otero-Ferrer; Fernando Tuya; Fernando Espino; Kathryn Schoenrock; Laurie C. Hofmann; Line Le Gall; et al. (Frontiers in Marine Science, 2022)
Coralline algae are important components in a large variety of ecosystems. Among them, rhodoliths are a group of free-living coralline red algae that cover extensive coastal areas, from tropical to polar regions. In contrast to other ecosystem engineers, limited research efforts preclude our understanding of their physiology, underlying mechanisms, drivers and potential differences related to species under varying environments. In this study, we investigated the photosynthetic and calcification mechanisms of six Atlantic rhodolith species from different latitudes, as well as intra-specific differences in one species from four locations. Laboratory incubations under varying light levels provided simultaneous photosynthesis- and calcification-irradiance curves, allowing the assessment of inter- and intra-specific differences on the coupling between these two processes. Stable isotope analysis and specific inhibitor experiments were performed to characterize and compare carbon-concentrating mechanisms (CCMs), as well as the involvement of specific ion-transporters for calcification. Our findings showed significant differences in rhodolith physiological mechanisms that were partially driven by local environmental conditions (light, temperature). High variability was found in the coupling between photosynthesis and calcification, in CCM-strategies, and in the importance of specific ion transporters and enzymes involved in calcification. While calcification was strongly correlated with photosynthesis in all species, the strength of this link was species-specific. Calcification was also found to be reliant on photosynthesis- and light-independent processes. The latter showed a high plasticity in their expression among species, also influenced by the local environment. Overall, our findings demonstrate that (1) rhodolith calcification is a biologically-controlled process and (2) the mechanisms associated with photosynthesis and calcification display a large variability among species, suggesting potential differences not only in their individual, but also community responses to environmental changes, such as climate change.

Quantifying protrusions as tumor-specific biophysical predictors of cancer invasion in in vitro tumor micro-spheroid models - D. Caballero; A. C. Lima; C. M. Abreu; N. M. Neves; V. M. Correlo; J. M. Oliveira; R. L. Reis; S. C. Kundu (In vitro models, 2022)

Groundwater response to climate variability in Mediterranean type climate zones with comparisons of California (USA) and Portugal - Katherine A. Malmgren; Maria C. Neves; Jason J. Gurdak; Luis Costa; José P. Monteiro (Hydrogeology Journal, 2022)

Keystone microbiome in the rhizosphere soil reveals the effect of long-term conservation tillage on crop growth in the Chinese Loess Plateau - Lijuan Jia; Zhen Wang; Lei Ji; Stefaan De Neve; Paul C. Struik; Yuqing Yao; Junjie Lv; Tao Zhou; Ke Jin (Plant and Soil, 2022)

Sperm whales exhibit variation in echolocation tactics with depth and sea state but not naval sonar exposures - Saana Isojunno; Alexander M. von Benda‐Beckmann; Paul J. Wensveen; Petter H. Kvadsheim; Frans‐Peter A. Lam; Kalliopi C. Gkikopoulou; Viivi Pöyhönen; Peter L. Tyack; Benjamin Benti; Ilias Foskolos; Jacqueline Bort; Miguel Neves; et al. (Marine Mammal Science, 2022)
Auditory masking by anthropogenic noise may impact marine mammals relying on sound for important life functions, including echolocation. Animals have evolved antimasking strategies, but they may not be completely effective or cost‐free. We formulated seven a priori hypotheses on how odontocete echolocation behavior could indicate masking. We addressed six of them using data from 15 tagged sperm whales subject to experimental exposures of pulsed and continuous active sonar (PAS and CAS). Sea state, received single‐pulse sound exposure level (SEL sp ), whale depth and orientation towards surface, and sonar were considered as candidate covariates representing different masking conditions. Echolocation behavior, including buzz duration and search range, varied strongly with depth. After controlling for depth and angle to the surface, the likelihood of buzzing following a click train decreased with sea state ( t = −7.3, p sp , except reduced buzzing consistent with previously reported feeding cessation ( t = −2.26, p = .02). A potential Lombard effect was detected during echolocation with sea state and SEL sp , despite off‐axis measurement and right‐hand censoring due to acoustic clipping. The results are not conclusive on masking effects on sperm whale echolocation, highlighting challenges and opportunities for future anthropogenic masking studies.

Direct and indirect effects of ant–trophobiont interactions on the reproduction of a hummingbird-pollinated mistletoe - Vanessa C. M. Ferreira; Frederico S. Neves; Tadeu J. Guerra (Plant Ecology, 2022)

Identification of Glycycometus malaysiensis (for the first time in Brazil), Blomia tropicalis and Dermatophagoides pteronyssinus through multiplex PCR - Vítor S. Alves; Luis F. Salazar-Garcés; Leonardo F. Santiago; Paula L. C. Fonseca; Antônio M. S. Fernandes; Raphael C. Silva; Lorena M. Souza; Pedro P. R. S. Cunha; Marina F. C. Barbosa; Eric R. G. R. Aguiar; Luis G. C. Pacheco; Neuza M. Alcantara-Neves; et al. (Experimental and Applied Acarology, 2022)

A comparison of stereo-videos and visual census methods for assessing subtropical rocky reef fish assemblage - Fernanda A. Rolim; Pedro F. C. Rodrigues; Tim Langlois; Leonardo M. Neves; Otto B. F. Gadig (Environmental Biology of Fishes, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Underlying microevolutionary processes parallel macroevolutionary patterns in ancient neotropical mountains - Marcos Vinicius Dantas‐Queiroz; Tami da Costa Cacossi; Bárbara Simões Santos Leal; Cleber Juliano Neves Chaves; Thais N. C. Vasconcelos; Leonardo de Melo Versieux; Clarisse Palma‐Silva (Journal of Biogeography, 2021)
Aim Ancient climatic fluctuations are invoked as the main driving force that generates the astonishing biodiversity in ancient mountains. As a result, endemism and spatial turnover are usually high and few species are widespread amongst entire mountain ranges, precluding the understanding of origins of macroevolutionary patterns. Here, we used a species endemic to, but widespread in, one of the most species‐rich ancient mountains in the globe to test how environmental changes acted on and how their macroevolutionary patterns were shaped. Location Espinhaço Range, Eastern Brazil. Taxon Vriesea oligantha species complex (Bromeliaceae). Methods We compiled data for plastidial regions and nuclear microsatellites to assess genetic diversity, population structure, migration rates and phylogenetic relationships. Using temperature and precipitation variables, we modelled suitable areas for the present and the past, estimating corridors between isolated populations. We also implemented Bayesian demographic analyses to estimate ancient populations dynamics. Finally, we tested if population structure is driven by isolation by environment or by distance using a Bayesian modelling approach. Results Our results showed that the intraspecific divergence events of V . oligantha are older than those associated with the latest Pleistocene climatic oscillations, supporting the view that Quaternary climatic fluctuations are key components for understanding its population differentiation processes. Species distribution modelling estimated corridors between populations in the past, as also shown in the demographic analyses, depicting a major spatial reorganization during colder climates. Besides, the high genetic structure estimated results from both models of isolation by distance and by environment. Main conclusions V . oligantha is a remarkable model to test the effects of climatic oscillations over the biological community, since this species originated in the early‐Pleistocene, prevailing over several cycles of climatic fluctuations until today. The estimated demographic dynamics of V . oligantha agrees with the species‐pump mechanism, suggesting it as the main cause of speciation within the Espinhaço Range. Moreover, the phylogeographic patterns of V . oligantha reflect previously recognised spatial and temporal macroevolutionary patterns in the Espinhaço Range, providing insights into how microevolutionary processes may have given rise to this astonishing mountain biodiversity.

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

Reassessing the Use of Undecanoic Acid as a Therapeutic Strategy for Treating Fungal Infections - Antonio Rossi; Maíra P. Martins; Tamires A. Bitencourt; Nalu T. A. Peres; Carlos H. L. Rocha; Flaviane M. G. Rocha; João Neves-da-Rocha; Marcos E. R. Lopes; Pablo R. Sanches; Júlio C. Bortolossi; Nilce M. Martinez-Rossi (Mycopathologia, 2021)

The drifting dinoflagellate Ceratium furcoides (Levander) Langhans 1925: fundamental niche shift during global invasion - Rafael Lacerda Macêdo; Philip Russo; Raphael F. Corrêa; Odete Rocha; Luciano Neves dos Santos; Christina W. C. Branco (Hydrobiologia, 2021)

Using richness of native and non-native aquatic species along a climatic gradient to test the intermediate disturbance hypothesis - Luciano N. Santos; Ana Clara S. Franco; Joice S. de Souza; Igor C. Miyahira; Antonio Jailson S. Rodrigues; Isabela Cristina B. Gonçalves; Natascha Krepsky; Helga A. B. Monte; Clarissa Naveira; Tatiana M. B. Cabrini; Rayane R. S. Abude; Matheus Augusto; et al. (Hydrobiologia, 2021)

Anthropogenic and natural inputs of polycyclic aromatic hydrocarbons in the sediment of three coastal systems of the Brazilian Amazon - Edgar A. R. Lima; Patrícia A. Neves; Sambasiva R. Patchineelam; José Francisco B. R. da Silva; Luis R. Takiyama; César C. Martins; Rafael A. Lourenço; Satie Taniguchi; Vladimir O. Elias; Márcia C. Bícego (Environmental Science and Pollution Research, 2021)

How much leaf area do insects eat? A data set of insect herbivory sampled globally with a standardized protocol - Gisele M. Mendes; Fernando A. O. Silveira; Carolina Oliveira; Wesley Dáttilo; Roger Guevara; Betsabé Ruiz‐Guerra; Maria Gabriela Boaventura; Sershen; Syd Ramdhani; Shyam S. Phartyal; Sérvio P. Ribeiro; Victor Diniz Pinto; et al. (Ecology, 2021)
Herbivory is ubiquitous. Despite being a potential driver of plant distribution and performance, herbivory remains largely undocumented. Some early attempts have been made to review, globally, how much leaf area is removed through insect feeding. Kozlov et al., in one of the most comprehensive reviews regarding global patterns of herbivory, have compiled published studies regarding foliar removal and sampled data on global herbivory levels using a standardized protocol. However, in the review by Kozlov et al., only 15 sampling sites, comprising 33 plant species, were evaluated in tropical areas around the globe. In Brazil, which ranks first in terms of plant biodiversity, with a total of 46,097 species, almost half (43%) being endemic, a single data point was sampled, covering only two plant species. In an attempt to increase knowledge regarding herbivory in tropical plant species and to provide the raw data needed to test general hypotheses related to plant–herbivore interactions across large spatial scales, we proposed a joint, collaborative network to evaluate tropical herbivory. This network allowed us to update and expand the data on insect herbivory in tropical and temperate plant species. Our data set, collected with a standardized protocol, covers 45 sampling sites from nine countries and includes leaf herbivory measurements of 57,239 leaves from 209 species of vascular plants belonging to 65 families from tropical and temperate regions. They expand previous data sets by including a total of 32 sampling sites from tropical areas around the globe, comprising 152 species, 146 of them being sampled in Brazil. For temperate areas, it includes 13 sampling sites, comprising 59 species. Thus, when compared to the most recent comprehensive review of insect herbivory (Kozlov et al.), our data set has increased the base of available data for the tropical plants more than 460% (from 33 to 152 species) and the Brazilian sampling was increased 7,300% (from 2 to 146 species). Data on precise levels of herbivory are presented for more than 57,000 leaves worldwide. There are no copyright restrictions. Please cite this paper when using the current data in publications; the authors request to be informed how the data is used in the publications.

Dihydroquinoline derivative as a potential anticancer agent: synthesis, crystal structure, and molecular modeling studies - W. F. Vaz; J. M. F. Custodio; G. D. C. D’Oliveira; B. J. Neves; P. S. C. Junior; J. T. M. Filho; C. H. Andrade; C. N. Perez; E. P. Silveira-Lacerda; H. B. Napolitano (Molecular Diversity, 2021)

Cyclic lipopeptide‐producing Pseudomonas koreensis group strains dominate the cocoyam rhizosphere of a Pythium root rot suppressive soil contrasting with P . putida prominence in conducive soils - Feyisara Eyiwumi Oni; Niels Geudens; Joseph T. Onyeka; Oluwatoyin Faith Olorunleke; Ayodeji Ekundayo Salami; Olumide Owolabi Omoboye; Anthony Arguelles Arias; Amayana Adiobo; Stefaan De Neve; Marc Ongena; José C. Martins; Monica Höfte (Environmental Microbiology, 2020)
Summary Pseudomonas isolates from tropical environments have been underexplored and may form an untapped reservoir of interesting secondary metabolites. In this study, we compared Pseudomonas and cyclic lipopeptide (CLP) diversity in the rhizosphere of a cocoyam root rot disease (CRRD) suppressive soil in Boteva, Cameroon with those from four conducive soils in Cameroon and Nigeria. Compared with other soils, Boteva andosols were characterized by high silt, organic matter, nitrogen and calcium. Besides, the cocoyam rhizosphere at Boteva was characterized by strains belonging mainly to the P . koreensis and P . putida (sub)groups, with representations in the P . fluorescens , P . chlororaphis , P . jessenii and P . asplenii (sub)groups. In contrast, P . putida isolates were prominent in conducive soils. Regarding CLP diversity, Boteva was characterized by strains producing 11 different CLP types with cocoyamide A producers, belonging to the P . koreensis group, being the most abundant. However, putisolvin III‐V producers were the most dominant in the rhizosphere of conducive soils in both Cameroon and Nigeria. Furthermore, we elucidated the chemical structure of putisolvin derivatives—putisolvin III‐V, and described its biosynthetic gene cluster. We show that high Pseudomonas and metabolic diversity may be driven by microbial competition, which likely contributes to soil suppressiveness to CRRD.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Patterns of diversity in a metacommunity of bees and wasps of relictual mountainous forest fragments - Lucas Neves Perillo; Newton Pimentel de Ulhôa Barbosa; Ricardo R. C. Solar; Frederico de Siqueira Neves (Journal of Insect Conservation, 2020)

The Azores: A Mid-Atlantic Hotspot for Marine Megafauna Research and Conservation - Pedro Afonso; Jorge Fontes; Eva Giacomello; Maria C. Magalhães; Helen R. Martins; Telmo Morato; Verónica Neves; Rui Prieto; Ricardo S. Santos; Mónica A. Silva; Frédèric Vandeperre (Frontiers in Marine Science, 2020)

Bloodstream Infection of a Cancer Patient by Cystobasidium minutum: A Case Report and Literature Review - Cicero P. Inácio; Madi V. Diniz; Paulo Sergio R. Araújo; Marilane S. Barros; Melyna C. L. Andrade; Reginaldo G. Lima-Neto; Danielle Patrícia C. Macêdo; Rejane P. Neves (Mycopathologia, 2020)

Ant removal distance, but not seed manipulation and deposition site increases the establishment of a myrmecochorous plant - Tiago V. Fernandes; Lucas N. Paolucci; Ricardo R. C. Solar; Frederico S. Neves; Ricardo I. Campos (Oecologia, 2020)

Water diversion in Brazil threatens biodiversity - Vanessa S. Daga; Valter M. Azevedo-Santos; Fernando M. Pelicice; Philip M. Fearnside; Gilmar Perbiche-Neves; Lucas R. P. Paschoal; Daniel C. Cavallari; José Erickson; Ana M. C. Ruocco; Igor Oliveira; André A. Padial; Jean R. S. Vitule (Ambio, 2020)

Isotopes and geochemistry to assess shallow/thermal groundwater interaction in a karst/fissured-porous environment (Portugal): a review and reinterpretation - J. M. Marques; C. Matos; P. M. Carreira; M. O. Neves (Sustainable Water Resources Management, 2019)

Intraspecific Cuticular Chemical Profile Variation in the Social Wasp Mischocyttarus consimilis (Hymenoptera, Vespidae) - E. F. Neves; L. D. Lima; D. Sguarizi-Antonio; L. H. C. Andrade; S. M. Lima; S. E. Lima-Junior; W. F. Antonialli-Junior (Neotropical Entomology, 2019)

Large Aortic Prosthesis Fungal Vegetation Due to Candida parapsilosis: An Uncommon Presentation - Melyna C. Leite-Andrade; Cicero P. Inácio; Fernanda Calixto; Marcela Feitosa; Diana P. L. Sepulveda; Franz A. G. Santos; Maria Daniela S. Buonafina; Reginaldo G. Lima-Neto; Rejane P. Neves (Mycopathologia, 2019)

The impact of atmospheric teleconnections on the coastal aquifers of Ria Formosa (Algarve, Portugal) - Maria C. Neves; Luis Costa; Rui Hugman; José P. Monteiro (Hydrogeology Journal, 2019)

Unifying macroecology and macroevolution to answer fundamental questions about biodiversity - Brian J. McGill; Jonathan M. Chase; Joaquín Hortal; Isaac Overcast; Andrew J. Rominger; James Rosindell; Paulo A. V. Borges; Brent C. Emerson; Rampal S. Etienne; Michael J. Hickerson; D. Luke Mahler; Francois Massol; et al. (Global Ecology and Biogeography, 2019)
The study of biodiversity started as a single unified field that spanned both ecology and evolution and both macro and micro phenomena. But over the 20th century, major trends drove ecology and evolution apart and pushed an emphasis towards the micro perspective in both disciplines. Macroecology and macroevolution re‐emerged as self‐consciously distinct fields in the 1970s and 1980s, but they remain largely separated from each other. Here, we argue that despite the challenges, it is worth working to combine macroecology and macroevolution. We present 25 fundamental questions about biodiversity that are answerable only with a mixture of the views and tools of both macroecology and macroevolution.

Are Trechisporales ectomycorrhizal or non-mycorrhizal root endophytes? - Mary Luz Vanegas-León; Marcelo A. Sulzbacher; Andrea C. Rinaldi; Mélanie Roy; Marc-André Selosse; Maria Alice Neves (Mycological Progress, 2019)

Multiplatform Protein Detection and Quantification Using Glutaraldehyde-Induced Fluorescence for 3D Systems - Mariana I. Neves; Marco Araújo; Cristina C. Barrias; Pedro L. Granja; Aureliana Sousa (Journal of Fluorescence, 2019)

The Retina as a Window or Mirror of the Brain Changes Detected in Alzheimer’s Disease: Critical Aspects to Unravel - Samuel Chiquita; Ana C. Rodrigues-Neves; Filipa I. Baptista; Rafael Carecho; Paula I. Moreira; Miguel Castelo-Branco; António F. Ambrósio (Molecular Neurobiology, 2019)

Sustained mass coral bleaching (2016–2017) in Brazilian turbid-zone reefs: taxonomic, cross-shelf and habitat-related trends - Carolina D. Teixeira; Rodrigo L. L. Leitão; Felipe V. Ribeiro; Fernando C. Moraes; Leonardo M. Neves; Alex C. Bastos; Guilherme H. Pereira-Filho; Milton Kampel; Paulo S. Salomon; João A. Sá; Ludmilla N. Falsarella; Michelle Amario; et al. (Coral Reefs, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

First report of Loricifera from the North East Pacific Region, with the description of two new species - Ricardo C. Neves; Reinhardt M. Kristensen; Melissa Rohal; David Thistle; Martin V. Sørensen (Marine Biodiversity, 2019)

Atmospheric Influence Over the Residence Time in the Bahia Blanca Estuary, Argentina - Jorge O. Pierini; Francisco Javier Campuzano; Paulo C. Leitão; Eduardo A. Gómez; Ramiro J. Neves (Thalassas: An International Journal of Marine Sciences, 2019)

A dark side of cleaning symbiosis: manned submersible observations - Rodrigo L. Moura; Fernando C. Moraes; Gilberto M. Amado-Filho; Leonardo M. Neves; Alexandre D. Kassuga; Danielle D’Agostini; Alex C. Bastos (Marine Biodiversity, 2019)

Congruent spatial patterns of ant and tree diversity in Neotropical savannas - Heraldo L. Vasconcelos; Jonas B. Maravalhas; Karen C. Neves; Renata Pacheco; Jésica Vieira; Flávio C. Camarota; Thiago J. Izzo; Glein M. Araújo (Biodiversity and Conservation, 2019)

Increasing levels of supplementation for crossbred steers on pasture during the dry period of the year - Daniele Soares Barroso Neves; Robério Rodrigues Silva; Fabiano Ferreira da Silva; Laize Vieira Santos; George Abreu Filho; Sinvaldo Oliveira de Souza; Marceliana da C. Santos; Weder Jansen Rocha; Ana Paula Gomes da Silva; Mateus de Melo Lisboa; Maria Magna Silva Pereira; Venício Macedo Carvalho (Tropical Animal Health and Production, 2018)

Variable rate spraying application on cotton using an electronic flow controller - F. H. R. Baio; D. C. Neves; H. B. Souza; A. J. F. Leal; R. C. Leite; J. P. Molin; S. P. Silva (Precision Agriculture, 2018)

First report of Fusarium lacertarum causing cladode rot in Nopalea cochenellifera in Brazil - Michele F. Santiago; Alice M. G. Santos; Cícero P. Inácio; Amaro C. Lira Neto; Tereza C. Assis; Rejane P. Neves; Vinson P. Doyle; Josiene S. Veloso; Willie A. S. Vieira; Marcos P. S Câmara; Delson Laranjeira (Journal of Plant Pathology, 2018)

Scleroderma meridionale ectomycorrhizae on Halimium halimifolium: expanding the Mediterranean symbiotic repertoire - Marco Leonardi; Maria-Alice Neves; Ornella Comandini; Andrea C. Rinaldi (Symbiosis, 2018)

Assessing the effects of rainfall reduction on litterfall and the litter layer in phytophysiognomies of the Amazonia–Cerrado transition - Karine da S. Peixoto; Ben Hur Marimon-Junior; Kelen A. Cavalheiro; Naiane A. Silva; Eder C. das Neves; Renata Freitag; Henrique A. Mews; Marco Bruno X. Valadão; e Beatriz S. Marimon (Brazilian Journal of Botany, 2018)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

Is resource partitioning the key? The role of intra‐interspecific variation in coexistence among five small endemic fish species (Characidae) in subtropical rivers - Mayara P. Neves; Jislaine C. Da Silva; Dirceu Baumgartner; Gilmar Baumgartner; Rosilene L. Delariva (Journal of Fish Biology, 2018)
This study focused on intra and interspecific variations in the diet of small species in the Pelotas River, upper Uruguay River ecoregion. We tested the hypothesis that five small characids coexist via resource partitioning. Samplings were performed quarterly between August 2013 and May 2014 at 14 sites in the Pelotas River basin, using gillnets of different mesh sizes, seines, cast nets and electrofishing. In this study, the contents of 1,253 stomachs were analysed from Astyanax dissensus , A. paris , A. saguazu , A. xiru and Bryconamericus patriciae . The main food resources consumed were aquatic insects, leaves, seeds and detritus. There were significant seasonal intra and interspecific variations in the use of food resources by the five species. Permutational analysis of multivariate dispersions results indicated significant differences in individual intraspecific variability between the sampled periods, with the highest values found in November and February because of an increase in allochthonous resources (leaves and seeds). Besides this, significant differences in the proportions of consumption of allochthonous and autochthonous were observed. The trophic niche breadth was significantly different among the species, such that in August, the species had narrower niche breadths. In the other periods, the highest niche breadth values were due to an increase in the consumption of allochthonous items. Diet overlap was low (

Photobiomodulation Therapy Improves Acute Inflammatory Response in Mice: the Role of Cannabinoid Receptors/ATP-Sensitive K+ Channel/p38-MAPK Signalling Pathway - Laís M. S. Neves; Elaine C. D. Gonçalves; Juliana Cavalli; Graziela Vieira; Larissa R. Laurindo; Róli R. Simões; Igor S. Coelho; Adair R. S. Santos; Alexandre M. Marcolino; Maíra Cola; Rafael C. Dutra (Molecular Neurobiology, 2018)

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Seismic assessment of a heavy-timber frame structure with ring-doweled moment-resisting connections - Leonardo G. Rodrigues; Jorge M. Branco; Luís A. C. Neves; André R. Barbosa (Bulletin of Earthquake Engineering, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Neotropical savanna ants show a reversed latitudinal gradient of species richness, with climatic drivers reflecting the forest origin of the fauna - Heraldo L. Vasconcelos; Jonas B. Maravalhas; Rodrigo M. Feitosa; Renata Pacheco; Karen C. Neves; Alan N. Andersen (Journal of Biogeography, 2018)
Aim To evaluate the extent to which ant species richness in Neotropical savannas varies with macrogeographic variables, and to identify the potential climatic drivers of such variation. Location The Cerrado savanna biome of central Brazil, in a region spanning ca. 20° of latitude and 18°of longitude. Methods Standardized sampling of the arboreal and ground‐dwelling faunas was performed in 29 well‐preserved savanna sites using pitfall traps. Species were classified according to their habitat affinities: open‐savanna specialists, forest‐associated species or habitat generalists. We used generalized linear models to evaluate the importance of geographic (latitude, longitude and elevation) and climatic (mean temperature and three metrics of rainfall) variables as predictors of species richness. Results The total number of species recorded at each site varied more than twofold (from 59 to 144), and latitude was the best geographic correlate of overall species richness. However, contrary to the expected pattern, more species were found at higher than lower latitudes. This reversed latitudinal pattern of diversity occurred for both the arboreal and ground‐dwelling faunas, and for the habitat generalists and forest specialists. The savanna specialists showed a mid‐latitudinal peak in diversity. Overall, there was a significant positive association between rainfall and species richness, but the strength of this relationship varied with ant habitat affinity. Main conclusions The Cerrado ant fauna shows a reverse latitudinal gradient in species diversity, and this can be explained by increasing rainfall during the warmest months of the year (and therefore in plant productivity) with increasing latitude. The sensitivity of Cerrado ant diversity to declining rainfall contrasts with the high resilience to aridity of the Australian savanna ant fauna, and this reflects the contrasting evolutionary histories of these faunas. Our findings highlight the importance of historical processes as drivers of intercontinental contrasts in macroecological patterns.

Reduced population size does not affect the mating strategy of a vulnerable and endemic seabird - Cristina Nava; Verónica C. Neves; Malvina Andris; Marie-Pierre Dubois; Philippe Jarne; Mark Bolton; Joël Bried (The Science of Nature, 2017)

Testing the usefulness of hydrogen and compound-specific stable isotope analyses in seabird feathers: a case study in two sympatric Antarctic storm-petrels - Petra Quillfeldt; Simon Thorn; Benjamin Richter; Marcela Nabte; Nestor Coria; Juan F. Masello; Melanie Massaro; Verónica C. Neves; Marcela Libertelli (Marine Biology, 2017)

Magnetic resonance diffusion tensor imaging for the pedunculopontine nucleus: proof of concept and histological correlation - A. T. D. L. Alho; C. Hamani; E. J. L. Alho; R. E. da Silva; G. A. B. Santos; R. C. Neves; L. L. Carreira; C. M. M. Araújo; G. Magalhães; D. B. Coelho; M. C. Alegro; M. G. M. Martin; et al. (Brain Structure and Function, 2017)

Rolling resistance contribution to a road pavement life cycle carbon footprint analysis - Laura Trupia; Tony Parry; Luis C. Neves; Davide Lo Presti (The International Journal of Life Cycle Assessment, 2017)

Expression of the citrus CsTIP2;1 gene improves tobacco plant growth, antioxidant capacity and physiological adaptation under stress conditions - Cristina P. S. Martins; Diana M. Neves; Luciana C. Cidade; Amanda F. S. Mendes; Delmira C. Silva; Alex-Alan F. Almeida; Mauricio A. Coelho-Filho; Abelmon S. Gesteira; Walter S. Soares-Filho; Marcio G. C. Costa (Planta, 2017)

Functional Response and Matrix Population Model of Podisus nigrispinus (Dallas, 1851) (Hemiptera: Pentatomidae) fed on Chrysomya putoria (Wiedemann, 1818) (Diptera: Calliphoridae) as Alternative Prey - V W Botteon; J A Neves; W A C Godoy (Neotropical Entomology, 2017)

Transcriptome profiling of Symbion pandora (phylum Cycliophora): insights from a differential gene expression analysis - Ricardo C. Neves; Joao C. Guimaraes; Sebastian Strempel; Heinrich Reichert (Organisms Diversity & Evolution, 2017)

3-D distribution of the radioelements in the granitic rocks of northern and central Portugal and geothermal implications - R. Lamas; M. M. Miranda; A. J. S. C. Pereira; L. J. P. F. Neves; N. Ferreira; N. V. Rodrigues (Journal of Iberian Geology, 2017)

The expression patterns of aquaporin 9, vacuolar H+-ATPase, and cytokeratin 5 in the epididymis of the common vampire bat - Mariana M. Castro; Bongki Kim; Eric Hill; Maria C. Q. Fialho; Luciano C. H. P. Puga; Mariella B. Freitas; Sylvie Breton; Mariana Machado-Neves (Histochemistry and Cell Biology, 2017)

Ecosystem effects of invertebrate fisheries - Tyler D Eddy; Heike K Lotze; Elizabeth A Fulton; Marta Coll; Cameron H Ainsworth; Júlio Neves de Araújo; Catherine M Bulman; Alida Bundy; Villy Christensen; John C Field; Neil A Gribble; Mejs Hasan; et al. (Fish and Fisheries, 2017)
Since the 1950s, invertebrate fisheries catches have rapidly expanded globally to more than 10 million tonnes annually, with twice as many target species, and are now significant contributors to global seafood provision, export, trade and local livelihoods. Invertebrates play important and diverse functional roles in marine ecosystems, yet the ecosystem effects of their exploitation are poorly understood. Using 12 ecosystem models distributed worldwide, we analysed the trade‐offs of various invertebrate fisheries and their ecosystem effects as well as ecological indicators. Although less recognized for their contributions to marine food webs, our results show that the magnitude of trophic impacts of invertebrates on other species of commercial and conservation interest is comparable with those of forage fish. Generally, cephalopods showed the strongest ecosystem effects and were characterized by a strong top‐down predatory role. Lobster, and to a lesser extent, crabs, shrimp and prawns, also showed strong ecosystem effects, but at lower trophic levels. Benthic invertebrates, including epifauna and infauna, also showed considerable ecosystem effects, but with strong bottom‐up characteristics. In contrast, urchins, bivalves, and gastropods showed generally lower ecosystem effects in our simulations. Invertebrates also strongly contributed to benthic–pelagic coupling, with exploitation of benthic invertebrates impacting pelagic fishes and vice versa. Finally, on average, invertebrates produced maximum sustainable yield at lower levels of depletion (~45%) than forage fish (~65%), highlighting the need for management targets that avoid negative consequences for target species and marine ecosystems as a whole.

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Impact of sea-level rise on earthquake and landslide triggering offshore the Alentejo margin (SW Iberia) - M. C. Neves; C. Roque; K. M. Luttrell; J. T. Vázquez; B. Alonso (Geo-Marine Letters, 2016)

Angiotensin Converting Enzyme and Dipeptidyl Peptidase-IV Inhibitory, and Antioxidant Activities of a Blue Mussel ( Mytilus edulis ) Meat Protein Extract and Its Hydrolysates - Adriana C. Neves; Pádraigín A. Harnedy; Richard J. FitzGerald (Journal of Aquatic Food Product Technology, 2016)

Characterization of Ciprofloxacin-Resistant and Ciprofloxacin-Susceptible Uropathogenic Escherichia coli Obtained from Patients with Gynecological Cancer - Muniqui S. Capett; Patricia Vollú-Silva; Vanessa A. Melchiades; Luciana C. Bokehi; Fernanda M. Araújo; Ianick Souto Martins; Felipe P. G. Neves; Alice G. M. Gonzalez; Eric Oswald; Geraldo R. de Paula; Lenise A. Teixeira (Current Microbiology, 2016)

A sustained approach to environmental catalysis: Reutilization of chromium from wastewater - Bruna Silva; Isabel C. Neves; Teresa Tavares (Critical Reviews in Environmental Science and Technology, 2016)

Effects of algal mats on a tropical estuarine benthic system: sediment biogeochemistry and macrofauna - Ana P. M. C. Valença; Caroline C. C. Clemente; Julia R. Neves; Janilson F. Silva; Ranilson S. Bezerra; Mônica L. Botter-Carvalho; Paulo V. V. C. Carvalho; Paulo J. P. Santos (Hydrobiologia, 2016)

Responses of fish assemblages of sandy beaches to different anthropogenic and hydrodynamic influences - A. C. S. Franco; M. C. N. Ramos Chaves; M. P. B. Castel‐Branco; L. Neves Dos Santos (Journal of Fish Biology, 2016)
This study tested whether some attributes of the diversity, communities and populations of surf‐zone fish assemblages varied with different hydrodynamic and anthropogenic influences at four Guanabara Bay sandy beaches: Dentro (sheltered with limited human access), Fora (exposed with limited human access), Urca (sheltered with unlimited human access) and Vermelha (exposed with unlimited human access), between autumn 2011 and summer 2012. Twenty‐nine species and 1613 individuals were recorded from 76 trawls. The 10 most abundant species accounted for 94·5% of the total number, but only four species ( Diplodus argenteus , Harengula clupeola , Sardinella brasiliensis and Sphoeroides greeleyi ) were recorded at all four beaches, revealing a high level of species substitution. Fish assemblages differed not only for diversity attributes, but also at community and population levels, with lower values of the Shannon–Wiener index, richness and total fish abundance and biomass at Vermelha beach, and higher densities of Trachinotus carolinus , Atherinella brasiliensis and S. greeleyi related to beaches with high anthropogenic influence. The findings reveal that fish assemblages of Dentro, Fora, Urca and Vermelha beaches differed not only in response to hydrodynamic influences, but also due to the effects of different degrees of human interference ( i.e. presence of solid residues, population density and fishing impacts), emphasizing the importance of the sheltered and less anthropogenically affected beaches, as spawning, nursery and growth areas.

Ecology and evolution of plant diversity in the endangered campo rupestre: a neglected conservation priority - Fernando A. O. Silveira; Daniel Negreiros; Newton P. U. Barbosa; Elise Buisson; Flávio F. Carmo; Daniel W. Carstensen; Abel A. Conceição; Tatiana G. Cornelissen; Lívia Echternacht; G. Wilson Fernandes; Queila S. Garcia; Tadeu J. Guerra; et al. (Plant and Soil, 2016)

Climatic and geologic controls on the piezometry of the Querença-Silves karst aquifer, Algarve (Portugal) - Maria C. Neves; Luis Costa; José P. Monteiro (Hydrogeology Journal, 2016)

First account on kinorhynchs from Portugal, with the description of two new species: Echinoderes lusitanicus sp. nov. and E. reicherti sp. nov. - Ricardo C. Neves; Martin V. Sørensen; Maria Herranz (Marine Biology Research, 2016)

Laser stimulation of the acupoint ‘Zusanli’ (ST.36) on the radiopharmaceutical biodistribution in Wistar rats - Éric HFF Frederico; Ailton A Santos; Danúbia C Sá-Caputo; Rosane F Neves; Carlos AS Guimarães; Shyang Chang; Mario Bernardo-Filho (Journal of Biosciences, 2016)

Evaluation of a M-202 × Oryza nivara advanced backcross mapping population for seedling vigor, yield components and quality - Georgia C. Eizenga; Péricles C. F. Neves; Rolfe J. Bryant; Hesham A. Agrama; David J. Mackill (Euphytica, 2016)

Oxaprozin-Loaded Lipid Nanoparticles towards Overcoming NSAIDs Side-Effects - José Lopes-de-Araújo; Ana Rute Neves; Virgínia M. Gouveia; Catarina C. Moura; Cláudia Nunes; Salette Reis (Pharmaceutical Research, 2016)

Numerical Simulation of Soil Water Dynamics Under Stationary Sprinkler Irrigation With Mohid‐Land - Lucian Simionesei; Tiago B. Ramos; David Brito; Eduardo Jauch; Pedro C. Leitão; Carina Almeida; Ramiro Neves (Irrigation and Drainage, 2016)
Water distribution in sprinkler irrigation systems remains one of the most challenging problems in irrigation water management. Due to lack of water distribution uniformity, parts of a field may be over‐irrigated while others may be under‐irrigated, thus affecting root water and nutrient uptake and crop yield. The objective of this paper was to show the capabilities of the MOHID‐Land model in simulating soil water dynamics and maize growth under a stationary sprinkler irrigation system with low water distribution uniformity (56%). A 3D simulation domain (28 × 26 × 1 m) was defined to consider different water application rates at the soil surface and the variability of the soil hydraulic properties (two soil types). The model was able to take into account the effect of water distribution and soil variability on soil water content and fluxes, root water uptake reductions due to water stress, soil evaporation, leaf area index and total dry biomass. The resulting soil water balance revealed that irrigation inputs were lower (329 mm) than those theoretically defined to fulfil crop water requirements when the variable‐rate application of water was not considered (540 mm). Consequently, the range of variation of soil water stress in the simulation domain was relatively large (between 1 and 64%). MOHID‐Land has thus the potential of becoming an important tool for precision irrigation by focusing on site‐specific irrigation and crop management rather than the current field unit approach. Copyright © 2016 John Wiley & Sons, Ltd.

Deep-water bamboo coral forests in a muddy Arctic environment - Bárbara de Moura Neves; Evan Edinger; Claude Hillaire-Marcel; Esprit Heestand Saucier; Scott C. France; Margaret A. Treble; Vonda E. Wareham (Marine Biodiversity, 2015)

Erratum to: Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Leapfrog migration and habitat preferences of a small oceanic seabird, Bulwer's petrel ( Bulweria bulwerii ) - Raül Ramos; Víctor Sanz; Teresa Militão; Joël Bried; Verónica C. Neves; Manuel Biscoito; Richard A. Phillips; Francis Zino; Jacob González‐Solís (Journal of Biogeography, 2015)
Aim Our current understanding of migratory strategies and the reasons for their high variability along the phylogenetic tree remains relatively poor. Most of the hypotheses relating to migration have been formulated for terrestrial taxa; classically, oceanic migrations were considered as merely dispersive because of the scarcity of observations in the open ocean. We describe for the first time, the migration strategy of a small seabird, the Bulwer's petrel ( Bulweria bulwerii ), and provide new insights into the ecology and evolution of long‐distance marine migrations. Location Subtropical and tropical Atlantic Ocean. Methods Using cutting‐edge geolocators, we examined the year‐round distribution and at‐sea activity patterns of adult Bulwer's petrels sampled at five localities throughout the species' breeding range in the Atlantic, within the Azores, Salvages, Canary and Cape Verde archipelagos. We assessed the migratory connectivity of the species and its habitat use at population and metapopulation scales. Results Our results provide the first evidence of an oriented leapfrog migration in oceanic seabirds. Ecological niche models based on breeding‐season data effectively predicted that subtropical waters of the South Atlantic would be the preferred habitat for the northern populations of Bulwer's petrels during the non‐breeding season. Habitat modelling also highlighted similarities in distributions between the breeding and non‐breeding periods for the southern populations. Data on at‐sea activity patterns suggested that birds from the northern and southern populations behave differently during the breeding season, as well as in the northern and southern non‐breeding ranges during the non‐breeding period. Main conclusions These results indicate that specific habitat preferences, presumably related to differences in prey availability, explain the observed distributions and hence the pattern of leapfrog migration described for Bulwer's petrel. Our study demonstrates the utility of integrating diverse tracking data from multiple populations across international boundaries, and habitat modelling, for identifying important areas common to many marine species in the vast oceanic environments.

Neonatal Candidemia Caused by Candida haemulonii: Case Report and Review of Literature - Carolina M. Silva; Ana M. R. Carvalho-Parahym; Danielle P. C. Macêdo; Reginaldo G. Lima-Neto; Elaine C. Francisco; Analy S. A. Melo; Maria da Conceição M. Silva; Moacir B. Jucá; Luciana R. B. Mello; Rosemary M. J. Amorim; Rejane P. Neves (Mycopathologia, 2015)

Mobility and persistence of the herbicide fomesafen in soils cultivated with bean plants using SLE/LTP and HPLC/DAD - Anna I. G. Costa; Maria Eliana L. R. Queiroz; Antônio A. Neves; Roberta C. de Assis; Carlos E. S. dos Soares; Antônio A. da Silva; Leonardo D’Antonino; André F. de Oliveira; Carlos R. Bellato (Environmental Science and Pollution Research, 2015)

Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A Single Neurotoxic Dose of Methamphetamine Induces a Long-Lasting Depressive-Like Behaviour in Mice - Carlos D. Silva; Ana F. Neves; Ana I. Dias; Hugo J. Freitas; Sheena M. Mendes; Inês Pita; Sofia D. Viana; Paulo A. de Oliveira; Rodrigo A. Cunha; Carlos A. Fontes Ribeiro; Rui D. Prediger; Frederico C. Pereira (Neurotoxicity Research, 2014)

IL-4: an important cytokine in determining the fate of T cells - J. L. Silva-Filho; C. Caruso-Neves; A. A. S. Pinheiro (Biophysical Reviews, 2014)

Past and present trophic position and decadal changes in diet of Yellow-legged Gull in the Azores Archipelago, NE Atlantic - Patrícia I. Pedro; Jaime A. Ramos; Verónica C. Neves; Vítor H. Paiva (European Journal of Wildlife Research, 2013)

Acute effects of three Geitlerinema spp. (Cyanobacteria) extracts administrated in mice: symptoms and histopathological aspects - M. Rangel; R. L. Brunetti; A. N. Garcia; C. C. N. Cambui; G. A. A. Conserva; A. C. Neves; C. L. Sant’Anna; L. R. Carvalho (Phytochemistry Reviews, 2013)

Comparative study of putative 9-cis-epoxycarotenoid dioxygenase and abscisic acid accumulation in the responses of Sunki mandarin and Rangpur lime to water deficit - D. M. Neves; M. A. Coelho Filho; B. S. Bellete; M. F. G. F. Silva; D. T. Souza; W. dos S. Soares Filho; M. G. C. Costa; A. S. Gesteira (Molecular Biology Reports, 2013)

Ants of Three Adjacent Habitats of a Transition Region Between the Cerrado and Caatinga Biomes: The Effects of Heterogeneity and Variation in Canopy Cover - F S Neves; K S Queiroz-Dantas; W D da Rocha; J H C Delabie (Neotropical Entomology, 2013)

Ubiquitin–Proteasome System Impairment and MPTP-Induced Oxidative Stress in the Brain of C57BL/6 Wild-type and GSTP Knockout Mice - Andreia Neves Carvalho; Carla Marques; Elsa Rodrigues; Colin J. Henderson; C. Roland Wolf; Paulo Pereira; Maria João Gama (Molecular Neurobiology, 2013)

Genetic Variability of Beauveria bassiana and a DNA Marker for Environmental Monitoring of a Highly Virulent Isolate Against Cosmopolites sordidus - D. V. Ferri; C. F. Munhoz; P. M. O. Neves; L. M. Ferracin; D. Sartori; M. L. C. Vieira; M. H. P. Fungaro (Indian Journal of Microbiology, 2012)

Tauroursodeoxycholic Acid Prevents MPTP-Induced Dopaminergic Cell Death in a Mouse Model of Parkinson’s Disease - M. Castro-Caldas; A. Neves Carvalho; E. Rodrigues; C. J. Henderson; C. R. Wolf; C. M. P. Rodrigues; M. J. Gama (Molecular Neurobiology, 2012)

Diet and exercise training reduce blood pressure and improve autonomic modulation in women with prehypertension - Allan R. K. Sales; Bruno M. Silva; Fabricia J. Neves; Natália G. Rocha; Renata F. Medeiros; Renata R. T. Castro; Antonio C. L. Nóbrega (European Journal of Applied Physiology, 2012)

Saving energy using fuzzy control applied to a chiller: an experimental study - F. V. Silva; J. E. Schmitz; L. C. Neves Filho; A. M. F. Fileti; V. Silveira Júnior (Clean Technologies and Environmental Policy, 2012)

Antioxidant treatment protects against matrix metalloproteinase activation and cardiomyocyte injury during acute pulmonary thromboembolism - Ozelia Sousa-Santos; Evandro M. Neto-Neves; Karina C. Ferraz; Carla S. Ceron; Elen Rizzi; Raquel F. Gerlach; Jose E. Tanus-Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Glutathione S-Transferase pi Mediates MPTP-Induced c-Jun N-Terminal Kinase Activation in the Nigrostriatal Pathway - Margarida Castro-Caldas; Andreia Neves Carvalho; Elsa Rodrigues; Colin Henderson; C. Roland Wolf; Maria João Gama (Molecular Neurobiology, 2012)

Seismic vulnerability assessment and characterisation of the buildings on Faial Island, Azores - Filipe Neves; Aníbal Costa; Romeu Vicente; C. Sousa Oliveira; Humberto Varum (Bulletin of Earthquake Engineering, 2012)

In vitro inhibitory effect of trichostatin A on canine grade 3 mast cell tumor - Marcia Kazumi Nagamine; Daniel S. Sanches; Katia C. Pinello; Luciana Neves Torres; Gregory Mennecier; Andréia O. Latorre; Heidge Fukumasu; Maria Lucia Zaidan Dagli (Veterinary Research Communications, 2011)

Abundance of Jackfruit (Artocarpus heterophyllus) Affects Group Characteristics and Use of Space by Golden-Headed Lion Tamarins (Leontopithecus chrysomelas) in Cabruca Agroforest - Leonardo C. Oliveira; Leonardo G. Neves; Becky E. Raboy; James M. Dietz (Environmental Management, 2011)

Higher-level metazoan relationships: recent progress and remaining questions - Gregory D. Edgecombe; Gonzalo Giribet; Casey W. Dunn; Andreas Hejnol; Reinhardt M. Kristensen; Ricardo C. Neves; Greg W. Rouse; Katrine Worsaae; Martin V. Sørensen (Organisms Diversity & Evolution, 2011)

Isolation of Cellulolytic Fungi from Waste of Castor (Ricinus communis L.) - Polyanna N. Herculano; D. M. M. Lima; M. J. S. Fernandes; R. P. Neves; C. M. Souza-Motta; A. L. F. Porto (Current Microbiology, 2011)

Harmonisation of food categorisation systems for dietary exposure assessments among European children - M. De Neve; I. Sioen; P.E. Boon; C. Arganini; J. Moschandreas; J. Ruprich; L. Lafay; P. Amiano; D. Arcella; M. Azpiri; L. Busk; T. Christensen; et al. (Food Additives & Contaminants: Part A, 2010)

Genetic diversity and plant-growth related features of Burkholderia spp. from sugarcane roots - Danice M. Luvizotto; Joelma Marcon; Fernando D. Andreote; Francisco Dini-Andreote; Aline A. C. Neves; Welington L. Araújo; Aline A. Pizzirani-Kleiner (World Journal of Microbiology and Biotechnology, 2010)

The live-attenuated yellow fever vaccine 17D induces broad and potent T cell responses against several viral proteins in Indian rhesus macaques—implications for recombinant vaccine design - Philip A. Mudd; Shari M. Piaskowski; Patricia C. Costa Neves; Richard Rudersdorf; Holly L. Kolar; Christopher M. Eernisse; Kim L. Weisgrau; Marlon G. Veloso de Santana; Nancy A. Wilson; Myrna C. Bonaldo; Ricardo Galler; Eva G. Rakasz; et al. (Immunogenetics, 2010)

Comparison of Biomass and Nutrient Dynamics Between an Invasive and a Native Species in a Mediterranean Saltmarsh - J. P. Neves; M. P. Simões; L. F. Ferreira; M. Madeira; L. C. Gazarini (Wetlands, 2010)

Assessing Seismic Damage Through Stochastic Simulation of Ground Shaking: The Case of the 1998 Faial Earthquake (Azores Islands) - G. Zonno; C. S. Oliveira; M. A. Ferreira; G. Musacchio; F. Meroni; F. Mota-de-Sá; F. Neves (Surveys in Geophysics, 2010)

Genetic differences between wild and hatchery populations ofDiplodus sargus andD. vulgaris inferred from RAPD markers: implications for production and restocking programs design - J. C. Pereira; P. G. Lino; A. Leitão; S. Joaquim; R. Chaves; P. Pousãao-Ferreira; H. Guedes-Pinto; M. Neves dos Santos (Journal of Applied Genetics, 2010)

Influence of tide and waves on water renewal in Óbidos Lagoon, Portugal - Madalena S. Malhadas; Ramiro J. Neves; Paulo C. Leitão; Adélio Silva (Ocean Dynamics, 2010)

Are European starlings breeding in the Azores archipelago genetically distinct from birds breeding in mainland Europe? - Verónica C. Neves; Kate Griffiths; Fiona R. Savory; Robert W. Furness; Barbara K. Mable (European Journal of Wildlife Research, 2010)

Reproduction and dispersal of wing-clipped predatory stinkbugs, Podisus nigrispinus in cotton fields - Robério C. S. Neves; Jorge B. Torres; Lucia M. Vivan (BioControl, 2009)

Effects of freezing on bone histological morphology - Miguel Gustavo Setúbal Andrade; Camila Neves Sá; Antônio Márcio Teixeira Marchionni; Thereza Cristina Bório dos Santos C de Bittencourt; Moysés Sadigursky (Cell and Tissue Banking, 2008)

Responses of talitrid amphipods to a gradient of recreational pressure caused by beach urbanization - V. G. Veloso; G. Neves; M. Lozano; A. Perez‐Hurtado; C. G. Gago; F. Hortas; F. Garcia Garcia (Marine Ecology, 2008)
Demands for public outdoor recreation and urbanization are a potential source of environmental disturbances, particularly on sandy beaches. These habitats have therefore experienced rapid degradation worldwide. Talitrid amphipods, which are common inhabitants of sandy beaches, are probably good indicators of such disturbances. In this study, we evaluated the responses of the two amphipods Talitrus saltator and Atlantorchestoidea brasiliensis to human pressure on Spanish and a Brazilian beach, hypothesizing that disregarding species differences, their population sizes will decline under urbanized conditions. The Barra da Tijuca (Brazil) and Levante (Spain) beaches have mixed landscapes with varying levels of development, and each has a protected area (MPA) adjacent to urbanized sites. Numbers of talitrids as well as visitors were compared among sites on each beach. Talitrids were most abundant at the protected sites. This was true of both beaches, even though temporal patterns of human activity were quite different, with Levante experiencing sharp declines in the number of visitors during its harsh winter. Urbanized sites did not experience high Talitrid densities even during a period of low human pressure. On this basis, T. saltator and A. brasiliensis were considered good indicators of urbanization and recreational activities on sandy beaches. MPAs were found to be very important for the successful conservation of the talitrid populations. A feasible method of managing human pressure and thereby conserving beach biodiversity therefore seems to be the establishment of beach MPAs.

Genetic control of somatic embryogenesis induction in Eucalyptus globulus Labill. - G. Pinto; Y. -S. Park; L. Neves; C. Araújo; C. Santos (Plant Cell Reports, 2008)

Characterization of Monoolein-Based Lipoplexes Using Fluorescence Spectroscopy - J. P. Neves Silva; P. J. G. Coutinho; M. E. C. D. Real Oliveira (Journal of Fluorescence, 2008)

Saccharomyces cerevisiae strains from traditional fermentations of Brazilian cachaça: trehalose metabolism, heat and ethanol resistance - Cristina R. Vianna; Carol L. C. Silva; Maria J. Neves; Carlos A. Rosa (Antonie van Leeuwenhoek, 2008)

First report of bristleworm predator of the reef octocoral Carijoa riisei - J. R. B. Souza; H. A. Rodrigues; B. M. Neves; C. D. Perez (Coral Reefs, 2007)

Identification of a novel potential antigen for early-phase serodiagnosis of leptospirosis - Fernanda O. Neves; Patricia A. E. Abreu; Silvio A. Vasconcellos; Zenáide M. de Morais; Eliete C. Romero; Ana L. T. O. Nascimento (Archives of Microbiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Strong effects of various incidence and observation angles on spectrometric assessment of plumage colouration in birds - S. I. C. O. Santos; L. De Neve; J. T. Lumeij; M. I. Förschler (Behavioral Ecology and Sociobiology, 2007)

Primary production and nutrient content in two salt marsh species,Atriplex portulacoides L. andLimoniastrum monopetalum L., in Southern Portugal - J. P. Neves; L. F. Ferreira; M. P. Simões; L. C. Gazarini (Estuaries and Coasts, 2007)

A control taste aversion experiment on predators of roseate tern (Sterna dougallii) eggs - V. C. Neves; S. Panagiotakopoulos; R. W. Furness (European Journal of Wildlife Research, 2006)

Validation of the water offloading technique for diet assessment: an experimental study with Cory’s shearwaters (Calonectris diomedea) - Verónica C. Neves; Mark Bolton; Luís R. Monteiro (Journal of Ornithology, 2006)

Effects of Cu, Ni and Zn on Lettuce Grown in Metal-Enriched Vermicompost Amended Soil - C. P. Jordão; L. L. Fialho; P. R. Cecon; A. T. Matos; J. C. L. Neves; E. S. Mendonça; R. L. F. Fontes (Water, Air, & Soil Pollution, 2006)

Molecular Mobility in Glass Forming Fananserine: A Dielectric, NMR, and TMDSC Investigation - L. Carpentier; R. Decressain; A. De Gusseme; C. Neves; M. Descamps (Pharmaceutical Research, 2006)

Polymorphism of the bm86 Gene in South American Strains of the Cattle Tick Boophilus microplus - Sidimar Sossai; Ana P. Peconick; Policarpo A. Sales-Junior; Francismar C. Marcelino; Marlene I. Vargas; Elisangela S. Neves; Joaquín H. Patarroyo (Experimental and Applied Acarology, 2005)

A new heterobinuclear FeIIICuII complex with a single terminal FeIII–O(phenolate) bond. Relevance to purple acid phosphatases and nucleases - Mauricio Lanznaster; Ademir Neves; Adailton J. Bortoluzzi; Veronika V. E. Aires; Bruno Szpoganicz; Hernán Terenzi; Patricia Cardoso Severino; Julie M. Fuller; Simon C. Drew; Lawrence R. Gahan; Graeme R. Hanson; Mark J. Riley; et al. (JBIC Journal of Biological Inorganic Chemistry, 2005)

Detection of LEE 4 Region-Encoded Genes from Different Enteropathogenic and Enterohemorrhagic Escherichia coli Serotypes - Eliane C. Mairena; Bianca C. Neves; Luiz R. Trabulsi; Waldir P. Elias (Current Microbiology, 2004)

Contribution of biological nitrogen fixation to cowpea: a strategy for improving grain yield in the semi-arid region of Brazil - L. M. V. Martins; G. R. Xavier; F. W. Rangel; J. R. A. Ribeiro; M. C. P. Neves; L. B. Morgado; N. G. Rumjanek (Biology and Fertility of Soils, 2003)

Biochemical composition of three algal species proposed as food for captive freshwater mussels - Catherine M. Gatenby; David M. Orcutt; Daniel A. Kreeger; Bruce C. Parker; Vannessa A. Jones; Richard J. Neves (Journal of Applied Phycology, 2003)

Somatic embryogenesis and plant regeneration in Eucalyptus globulus Labill - Pinto G.; Santos C.; Neves L.; Araújo C. (Plant Cell Reports, 2002)

Processing of ovine cardiac valve allografts: 3. Implantation following antimicrobial treatment and preservation. - J. Neves; M. Abecassis; T. Santiago; T. Ramos; J. Melo; E. Gruys; C. Hulskamp-Koch; A. Ultee; E.L.C. Verkaar; J.A. Lenstra; Y.A. Goffin; A. Vanderkelen; et al. (Cell and Tissue Banking, 2002)

Central injections of noradrenaline and adrenaline differentially affect plasma free fatty acid and glucose in conscious pigeons ( Columba livia ) - J. das Neves; L. P. N. Hackl; C. G. Freitas; M. A. Paschoalini; J. Marino-Neto (Journal of Comparative Physiology B, 2000)

Edaphic factors as determinants for the distribution of intrinsic antibiotic resistance in a cowpea rhizobia population - G. R. Xavier; L. M. V. Martins; M. C. P. Neves; N. G. Rumjanek (Biology and Fertility of Soils, 1998)

Induction and inhibition of human lymphocyte transformation by the lectin from the red marine alga Amansia multifida - Hermenio C. Lima; Francisco H. F. Costa; Alexandre H. Sampaio; Samya A. Neves; Norma M. B. Benevides; Darlio I. A. Teixeira; David J. Rogers; Ana Lúcia P. Freitas (Journal of Applied Phycology, 1998)